Catalyst precursor and method for producing same, catalyst molded body and method for producing same, method for producing catalyst, method for producing alpha, beta-unsaturated carboxylic acid, and method for producing alpha, beta-unsaturated carboxylic acid ester
By using a specific design catalyst precursor or molded body with pore volume and pore distribution, the problem of insufficient yield of existing catalysts is solved, and efficient manufacturing of α,β-unsaturated carboxylic acids is achieved.
Patent Information
- Application Number
- CN202380062391.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-01
- Filing Date
- 2023-08-31
- Publication Date
- 2025-04-08
AI Technical Summary
The yield of existing catalysts is insufficient in the manufacturing process of α,β-unsaturated carboxylic acids, and it is difficult to meet the need to further improve the performance of the catalyst.
The structure and properties of the catalyst are optimized by using a catalyst precursor with a pore volume of 0.005 to 0.15 mL/g or a catalyst molded body with a specific pore volume and pore distribution.
The yield of α,β-unsaturated carboxylic acid is significantly improved, and the performance and efficiency of the catalyst are improved.
Smart Images

Figure CN119789909A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a catalyst precursor and a method for producing the same, a catalyst molded body and a method for producing the same, a method for producing a catalyst, a method for producing an α,β-unsaturated carboxylic acid, and a method for producing an α,β-unsaturated carboxylic acid ester. Background Art
[0002] As a catalyst for the manufacture of α,β-unsaturated carboxylic acid (hereinafter, also referred to as "catalyst") used when α,β-unsaturated aldehydes are oxidized to manufacture α,β-unsaturated carboxylic acids, heteropolyacid catalysts such as phosphomolybdic acid are known. A large number of studies have been conducted on the manufacturing method of heteropolyacid catalysts, most of which first prepare an aqueous solution or slurry containing each element constituting the catalyst, then dry it to manufacture a catalyst precursor, and manufacture the catalyst by molding and / or calcining the catalyst precursor. It is known that the physical properties of the catalyst precursor and the particle size of the catalyst obtained at this time, the specific surface area of the catalyst obtained, etc., vary according to the preparation conditions and drying conditions of the slurry, which will affect the catalyst performance.
[0003] Patent Document 1 describes a method for producing a methacrylic acid production catalyst, which is used when producing methacrylic acid by gas-phase catalytic oxidation of methacrolein with molecular oxygen and contains at least molybdenum and phosphorus as catalyst components.
[0004] In addition, in the production of α,β-unsaturated carboxylic acids, the catalyst is generally molded into a spherical shape with a diameter of about 2 to 20 mm, or a cylindrical or cylindrical molded body with a diameter of about 2 to 10 mm and a length of about 2 to 20 mm, and is filled into a reactor for use in the form of a catalyst molded body. It is known that the performance of the catalyst molded body varies depending on the pore structure, and many studies have been conducted to control the pore structure of the catalyst molded body.
[0005] Patent Document 2 describes a catalyst for producing methacrylic acid, which has a pore volume of 0.10 to 1.0 cc / g and a pore distribution in which pore diameters are concentrated in the ranges of 1 to 10 μm and 0.1 to 1 μm, respectively.
[0006] Patent Document 3 describes a catalyst for producing methacrylic acid, which is characterized in having at least two peaks in a pore radius range of 0.5 to 10 μm in a pore size distribution diagram.
[0007] Patent Document 4 describes a method for producing a catalyst for producing methacrylic acid containing at least molybdenum and phosphorus as catalyst components, which is used when producing methacrylic acid by gas-phase catalytic oxidation of methacrolein with molecular oxygen. When the ratio of the apparent density of a dried product to the density of a molded product is within a specific range, both the amount of pores effective for selective oxidation of methacrolein and the amount of catalyst filled effective for oxidation of methacrolein can be ensured, thereby improving the yield of methacrylic acid.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2011-224482
[0011] Patent Document 2: Japanese Patent Application Publication No. 63-315148
[0012] Patent Document 3: Japanese Patent Application Publication No. 2000-84412
[0013] Patent Document 4: International Publication No. 2012 / 141076 Summary of the invention
[0014] However, the catalysts described in Patent Documents 1 to 4 do not necessarily provide sufficient yields of α,β-unsaturated carboxylic acids. Therefore, from the viewpoint of further improving catalyst performance, it is necessary to develop a catalyst having physical properties more suitable for producing α,β-unsaturated carboxylic acids.
[0015] The present inventors have conducted intensive studies in view of the above problems and have found that the above problems can be solved by using a catalyst precursor having a specific pore volume or a catalyst molded body having a specific pore volume and pore distribution, thereby completing the present invention.
[0016] That is, the present invention includes the following aspects.
[0017] [1]: A catalyst precursor, which is a catalyst precursor comprising a Keggin-type heteropoly acid used when oxidizing an α,β-unsaturated aldehyde to produce an α,β-unsaturated carboxylic acid.
[0018] Its pore volume is 0.005 to 0.15 mL / g.
[0019] [2]: The catalyst precursor according to [1], wherein the median particle size is 1 to 50 μm.
[0020] [3]: The catalyst precursor according to [2], wherein the median particle size is 5 to 40 μm.
[0021] [4]: The catalyst precursor according to any one of [1] to [3], wherein the pore volume is 0.01 to 0.10 mL / g.
[0022] [5]: The catalyst precursor according to any one of [1] to [4], wherein the bulk density is 1.15 to 1.6 kg / L.
[0023] [6]: The catalyst precursor according to any one of [1] to [5], which has a composition represented by the following formula (I),
[0024] P a Mo b V c Cu d A e E f G g (NH4) h O i (I)
[0025] (In formula (I), P, Mo, V, Cu, NH4 and O represent phosphorus, molybdenum, vanadium, copper, ammonium and oxygen, respectively. A represents at least one element selected from antimony, bismuth, arsenic, germanium, tellurium, selenium, silicon and tungsten. E represents at least one element selected from iron, zinc, chromium, tantalum, cobalt, nickel, manganese, titanium, niobium and cerium. G represents at least one element selected from lithium, sodium, potassium, rubidium and cesium. a to i represent the molar ratio of each component, satisfying b=12, a=0.5-3, c=0.01-3, d=0.01-2, e=0-3, f=0-3, g=0.01-3, h=1-30, and i is the molar ratio of oxygen required to satisfy the valence of each of the above components.)
[0026] [7]: A molded catalyst body, which is used when producing an α,β-unsaturated carboxylic acid by oxidizing an α,β-unsaturated aldehyde, and contains a catalyst component containing phosphorus, molybdenum and vanadium.
[0027] Its pore volume is 0.01~0.40mL / g,
[0028] In the pore distribution curve of the catalyst molded body, when the height of the highest peak (peak A) having a vertex in the pore diameter range of 0.05 to 10 μm is IA and the height of the second highest peak (peak B) is IB, IB / IA is 0.160 to 0.420.
[0029] [8]: The catalyst molded body according to [7], wherein the IB / IA is 0.200 to 0.400.
[0030] [9]: The catalyst molded body according to [7] or [8], wherein the specific surface area is 1 to 10 m 2 / g.
[0031]
[10] : The catalyst molded body according to [9], wherein the specific surface area is 1.5 to 8 m 2 / g.
[0032]
[11] : The catalyst molded body according to any one of [7] to
[10] , wherein the pore volume is 0.10 to 0.35 mL / g.
[0033]
[12] : The catalyst molded body according to any one of [7] to
[11] , wherein the apexes of the peak A and the peak B exist in a pore diameter range of 0.08 to 8 μm.
[0034]
[13] : The catalyst molded body according to any one of [7] to
[12] , which is an extruded molded body.
[0035]
[14] : A method for producing a catalyst precursor, which is the method for producing a catalyst precursor according to any one of [1] to [6], comprising:
[0036] Step (i), obtaining a solution or slurry (liquid A1) containing phosphorus, molybdenum and vanadium,
[0037] Step (ii), adding a raw material compound (compound B) containing ammonium radicals to the above-mentioned A1 solution to obtain a slurry (A2 solution) having a pH of 3 or less, and
[0038] Step (iii), drying the above-mentioned A2 liquid to obtain dry particles,
[0039] In the above step (ii), compound B is added so as to satisfy the following formula (II).
[0040] v / M=0.10~1.80(II)
[0041] (In formula (II), M is the number of moles of molybdenum contained in the A1 solution (mol), and v is the addition rate of ammonium radicals (mol / h).)
[0042]
[15] : A method for producing a catalyst molded body, comprising obtaining a catalyst molded body from a catalyst precursor produced by the method described in
[14] ,
[0043] The method comprises the step (iv) of extruding the dried particles to obtain a catalyst molded body.
[0044]
[16] : A method for producing a catalyst, comprising calcining the catalyst precursor described in any one of [1] to [6] or the catalyst precursor produced by the method described in
[14] .
[0045]
[17] : A method for producing a catalyst molded body, which is the method for producing a catalyst molded body according to any one of [7] to
[13] , comprising:
[0046] Step (i), obtaining a solution or slurry (liquid A1) containing phosphorus, molybdenum and vanadium,
[0047] Step (ii), adding a raw material compound (compound B) containing ammonium radicals to the above-mentioned A1 solution to obtain a slurry (A2 solution) having a pH of 3 or less,
[0048] Step (iii), drying the A2 solution to obtain dry particles, and
[0049] Step (iv), extruding the dried particles to obtain a catalyst molded body,
[0050] In the above step (ii), compound B is added so as to satisfy the following formula (II).
[0051] v / M=0.10~1.80(II)
[0052] (In formula (II), M is the number of moles of molybdenum contained in the A1 solution (mol), and v is the addition rate of ammonium radicals (mol / h).)
[0053]
[18] : The method for producing a catalyst molded body according to
[15] or
[17] , wherein the solid content concentration of the above-mentioned A2 liquid is 30% by mass or less.
[0054]
[19] : A method for producing a catalyst molded body according to any one of
[15] and
[17] to
[18] , wherein when the ratio of the total mass of dissolved molybdenum, phosphorus and vanadium to the total mass of molybdenum, phosphorus and vanadium in the above-mentioned A2 liquid is set to R, R is 5 to 25 mass%.
[0055]
[20] : The method for producing a catalyst molded body according to any one of
[15] and
[17] to
[19] , wherein in the step (ii), the compound B is added to the A1 solution at a temperature of 90 to 99°C while stirring at a rotation speed of 70 to 140 rpm.
[0056]
[21] : The method for producing a catalyst molded body according to any one of
[15] and
[17] to
[20] , wherein in the step (iii), the A2 liquid is spray-dried.
[0057]
[22] : The method for producing a catalyst molded body according to any one of
[15] and
[17] to
[21] , wherein the step (iv) comprises the following steps (iv-1) and (iv-2):
[0058] In step (iv-1), the dry particles, liquid and a binder are mixed to obtain a kneaded product.
[0059] In step (iv-2), the kneaded product is extruded and molded using an extruder to obtain a catalyst molded body.
[0060]
[23] : The method for producing a catalyst molded body according to
[22] , wherein in the step (iv-1), 15 to 60 parts by mass of the liquid and 0.05 to 15 parts by mass of the binder are mixed with 100 parts by mass of the dry particles.
[0061]
[24] : The method for producing a catalyst molded body according to
[22] or
[23] , wherein in the above (iv-2), the extrusion molding is carried out at an extrusion pressure of 0.1 to 30 MPa.
[0062]
[25] A method for producing an α,β-unsaturated carboxylic acid, comprising oxidizing an α,β-unsaturated aldehyde using a catalyst obtained by molding and / or calcining the catalyst precursor described in any one of [1] to [6], or a catalyst molded body described in any one of [7] to
[13] to produce an α,β-unsaturated carboxylic acid.
[0063]
[26] A method for producing an α,β-unsaturated carboxylic acid ester, comprising esterifying the α,β-unsaturated carboxylic acid produced by the method described in
[25] .
[0064] According to the present invention, a catalyst precursor or a catalyst molded body capable of producing a catalyst with a high yield of α,β-unsaturated carboxylic acid can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 It is a graph showing the pore distribution curves of the catalyst precursors in Example 1-1, Example 1-4, and Comparative Example 1-1.
[0066] Figure 2 It is a graph showing the cumulative pore volume curves of the catalyst precursors in Example 1-1, Example 1-4, and Comparative Example 1-1. DETAILED DESCRIPTION
[0067] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following.
[0068] In addition, in this specification, the numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit, and "A to B" means A or more and B or less.
[0069] [Catalyst precursor]
[0070] The catalyst precursor of the present embodiment is a catalyst precursor used when oxidizing an α,β-unsaturated aldehyde to produce an α,β-unsaturated carboxylic acid, and is a catalyst precursor containing a Keggin-type heteropolyacid and having a pore volume of 0.005 to 0.15 mL / g. By using a catalyst produced from such a catalyst precursor, an α,β-unsaturated carboxylic acid can be produced at a high yield.
[0071] <Composition of Catalyst Precursor>
[0072] The catalyst precursor of the present embodiment includes a Keggin type heteropoly acid. As a method for obtaining a catalyst precursor including a Keggin type heteropoly acid, for example, there is a method in which a catalyst precursor is produced by the production method described below and the pH of the A2 solution is adjusted to 3 or less in step (ii).
[0073] Whether the catalyst precursor contains a Keggin-type heteropolyacid can be confirmed by infrared absorption analysis using NICOLET6700FT-IR (product name, manufactured by Thermo Electron) or the like, or X-ray diffraction analysis using an X-ray diffractometer such as X'Pert PRO MPD (product name, manufactured by PANaltical) or the like.
[0074] The catalyst precursor of the present embodiment preferably contains phosphorus, molybdenum and vanadium. From the viewpoint of increasing the yield of α,β-unsaturated carboxylic acid, the ratio of the number of phosphorus atoms when the number of molybdenum atoms is set to 12 is preferably 0.5 to 3, and the lower limit is more preferably 0.6 or more, further preferably 0.7 or more, and particularly preferably 0.8 or more. The upper limit is more preferably 2.5 or less, and further preferably 2 or less. In addition, the ratio of the number of vanadium atoms when the number of molybdenum atoms is set to 12 is preferably 0.01 to 3, and the lower limit is more preferably 0.05 or more, further preferably 0.1 or more, and particularly preferably 0.2 or more. The upper limit is more preferably 2.5 or less, further preferably 2 or less, and particularly preferably 1.5 or less.
[0075] From the viewpoint of increasing the yield of the α,β-unsaturated carboxylic acid, the catalyst precursor of the present embodiment particularly preferably has a composition represented by the following formula (I). The catalyst precursor may contain a small amount of elements not described in the following formula (I).
[0076] P a Mo b V c Cu d A e E f G g (NH4) h O i (I)
[0077] In formula (I), P, Mo, V, Cu, NH4 and O represent phosphorus, molybdenum, vanadium, copper, ammonium and oxygen, respectively. A represents at least one element selected from antimony, bismuth, arsenic, germanium, tellurium, selenium, silicon and tungsten. E represents at least one element selected from iron, zinc, chromium, tantalum, cobalt, nickel, manganese, titanium, niobium and cerium. G represents at least one element selected from lithium, sodium, potassium, rubidium and cesium. a~i represent the molar ratio of each component, satisfying b=12, a=0.5~3, c=0.01~3, d=0.01~2, e=0~3, f=0~3, g=0.01~3, h=1~30, and i is the molar ratio of oxygen required to satisfy the valence of each of the above components.
[0078] In the above formula (I), G is preferably at least one element selected from potassium and cesium from the viewpoint of improving the activity and life of the catalyst.
[0079] In the above formula (I), from the viewpoint of increasing the yield of α,β-unsaturated carboxylic acid, the lower limit of a is preferably 0.6 or more, more preferably 0.7 or more, and further preferably 0.8 or more. In addition, the upper limit of a is preferably 2.5 or less, and more preferably 2 or less. The lower limit of c is preferably 0.05 or more, preferably 0.1 or more, and further preferably 0.2 or more. In addition, the upper limit of c is preferably 2.5 or less, more preferably 2 or less, and further preferably 1.5 or less. The lower limit of d is preferably 0.03 or more, more preferably 0.05 or more, and further preferably 0.1 or more. In addition, the upper limit of d is preferably 1.5 or less, and further preferably 1 or less. The lower limit of e is preferably 0.01 or more, and more preferably 0.1 or more. In addition, the upper limit of e is preferably 2.5 or less, and further preferably 2 or less. The lower limit of f is preferably 0.01 or more, and more preferably 0.03 or more. In addition, the upper limit of f is preferably 2 or less, and more preferably 1.5 or less, and further preferably 1 or less. The lower limit of g is preferably 0.1 or more, more preferably 0.3 or more, and further preferably 0.5 or more. In addition, the upper limit of g is preferably 2.8 or less, more preferably 2.5 or less, and further preferably 2 or less. The lower limit of h is preferably 2 or more, more preferably 3 or more. In addition, the upper limit of h is preferably 20 or less, and more preferably 10 or less.
[0080] It should be noted that the molar ratio of each component is a value obtained by analyzing the components obtained by dissolving the catalyst precursor in ammonia water using ICP emission spectroscopy. In addition, the molar ratio of ammonium radicals is a value obtained by analyzing the catalyst precursor using the Kjeldahl method. Here, in the present invention, "ammonium radicals" are ammonia (NH3) and ammonium ions (NH4 + ) is a general term for ).
[0081] <Pore volume of catalyst and catalyst precursor>
[0082] The specific surface area of the catalyst is increased by increasing the pore volume of the catalyst. As a result, the activity of the catalyst is improved and the yield of α,β-unsaturated carboxylic acid is improved. On the other hand, if the pore volume of the catalyst is too large, the filling density of the catalyst is reduced, resulting in a reduction in the weight of the catalyst that can be filled into a reactor of a certain volume. Therefore, sufficient catalytic activity cannot be obtained, and the yield of α,β-unsaturated carboxylic acid is reduced. That is, by increasing the pore volume, both the increase and decrease of the yield of α,β-unsaturated carboxylic acid can be obtained, so it has been difficult to sufficiently increase the yield of α,β-unsaturated carboxylic acid by controlling the pore volume of the catalyst. Therefore, in the present invention, the pore volume of the catalyst suitable for the manufacture of α,β-unsaturated carboxylic acid is studied.
[0083] The pore volume of the catalyst precursor of the present embodiment is 0.005 to 0.15 mL / g. By making the pore volume 0.005 mL / g or more, the specific surface area of the catalyst manufactured from the catalyst precursor becomes sufficiently large, and the yield of α, β-unsaturated carboxylic acid is improved. In addition, by making the pore volume less than 0.15 mL / g, the packing density of the catalyst manufactured from the catalyst precursor becomes sufficiently large, and the weight of the catalyst that can be filled into a reactor of a certain volume increases, so the yield of α, β-unsaturated carboxylic acid is improved. The lower limit of the pore volume is preferably 0.01 mL / g or more, and more preferably 0.05 mL / g or more. In addition, the upper limit is preferably 0.10 mL / g or less, and more preferably 0.09 mL / g or less.
[0084] In the present embodiment, the pore volume of the catalyst precursor refers to the pore volume in the particles of the catalyst precursor. The pore volume of the catalyst precursor can be measured using a mercury intrusion pore distribution measuring device. As a mercury intrusion pore distribution measuring device, for example, AutoPore IV-9500 (product name, micromeritics system) can be cited. It should be noted that in the mercury intrusion pore distribution measurement, not only the pore volume of the catalyst precursor of the present embodiment, that is, the pore volume in the particles of the catalyst precursor, is measured, but also the pore volume of the physical gap between the particles of the catalyst precursor is measured. The pore volume of the catalyst precursor of the present embodiment is calculated based on the pore volume with a pore diameter of less than 0.5 μm.
[0085] As a method for obtaining a catalyst precursor having a pore volume within the above-mentioned range, for example, there can be cited a method of producing a catalyst precursor using the production method described later and adjusting the addition rate v (mol / h) of compound B, the temperature of liquid A1 and the stirring speed of liquid A1 in step (ii), a method of adjusting the physical properties of liquid A2, and a method of adjusting the drying conditions in step (iii).
[0086] <Median particle size of catalyst precursor>
[0087] The median particle size of the catalyst precursor of the present embodiment is preferably 1 to 50 μm. By making the median particle size of the catalyst precursor greater than 1 μm, the α,β-unsaturated aldehyde as a raw material and the generated α,β-unsaturated carboxylic acid can be fully diffused in the pores derived from the particles of the catalyst manufactured from the catalyst precursor, so the yield of α,β-unsaturated carboxylic acid is improved. In addition, by making the median particle size of the catalyst precursor less than 50 μm, the reaction matrix can easily diffuse into the catalyst particles manufactured from the catalyst precursor, and a higher yield of α,β-unsaturated carboxylic acid can be obtained even when the pore volume is small. The lower limit of the median particle size is more preferably greater than 5 μm, and more preferably greater than 10 μm. In addition, the upper limit is more preferably less than 40 μm, and more preferably less than 30 μm.
[0088] It should be noted that in the present invention, the median particle size refers to the particle size equivalent to the cumulative 50 volume % in the volume-based particle size distribution measured by the laser diffraction particle size distribution determination method, for example, it can be measured using a laser diffraction wet particle size distribution determination device or a laser diffraction dry particle size distribution determination device. As a laser diffraction wet particle size distribution determination device, for example, LA-700 (product name, manufactured by Horiba), LA-900 (product name, manufactured by Horiba), LA-960V2 (product name, manufactured by Horiba), SALD-7000 (product name, manufactured by Shimadzu), etc. can be cited. In addition, as a laser diffraction dry particle size distribution determination device, SALD-2300 (product name, manufactured by Shimadzu) can be cited.
[0089] As a method for obtaining a catalyst precursor having a median particle size within the above-mentioned range, for example, there can be cited a method of manufacturing a catalyst precursor using the manufacturing method described later and adjusting the addition rate v (mol / h) of compound B, the temperature of liquid A1 and the stirring speed of liquid A1 in step (ii), a method of adjusting the physical properties of liquid A2, and a method of adjusting the drying conditions in step (iii).
[0090] <Bulk density of catalyst precursor>
[0091] The bulk density of the catalyst precursor of the present embodiment is preferably 1.15 to 1.6 kg / L. By making the bulk density of the catalyst precursor 1.15 kg / L or more, when the catalyst manufactured from the catalyst precursor is filled into a reactor of a certain volume, the weight of the catalyst that can be filled increases, so that sufficient catalytic activity can be obtained in the manufacture of α, β-unsaturated carboxylic acids. In addition, by making the bulk density of the catalyst precursor 1.6 kg / L or less, the specific surface area of the catalyst manufactured from the catalyst precursor becomes sufficiently large, and the yield of α, β-unsaturated carboxylic acids is improved. The lower limit of the bulk density of the catalyst precursor is more preferably 1.2 kg / L or more, and more preferably 1.25 kg / L or more. The upper limit of the bulk density of the catalyst precursor is more preferably 1.55 kg / L or less, and more preferably 1.5 kg / L or less.
[0092] In the present invention, the bulk density of the catalyst precursor is calculated by measuring the catalyst precursor in a 50 mL measuring cylinder and calculating the bulk density from the mass in a volume of 50 mL using the following formula.
[0093] Bulk density of catalyst precursor (kg / L) = weight of catalyst precursor filled in 50mL measuring cylinder (g) / 50 (mL)
[0094] [Method for producing catalyst precursor]
[0095] The catalyst precursor of the present embodiment can be produced by a known method for producing a catalyst precursor as long as it contains a Keggin-type heteropolyacid and has a pore volume of 0.005 to 0.15 mL / g, and is preferably produced by the method for producing a catalyst precursor of the present embodiment including the following steps (i) to (iii).
[0096] In step (i), a solution or slurry (liquid A1) containing phosphorus, molybdenum and vanadium is obtained.
[0097] In step (ii), a raw material compound (compound B) containing an ammonium group is added to the above-mentioned A1 solution to obtain a slurry (A2 solution) having a pH of 3 or less.
[0098] In step (iii), the A2 solution is dried to obtain dry particles.
[0099] Hereinafter, each step will be described in detail.
[0100] <Step (i)>
[0101] In step (i), a solution or slurry (liquid A1) containing phosphorus, molybdenum and vanadium is obtained. Liquid A1 may also contain other elements, such as Cu (copper), element A, element E, and element G in formula (I). It should be noted that other elements other than phosphorus, molybdenum and vanadium in formula (I) may also be added in steps after step (i).
[0102] Liquid A1 can be prepared by dissolving or suspending a raw material compound of a catalyst precursor component containing phosphorus, molybdenum and vanadium in a solvent.
[0103] (Raw material compound of catalyst precursor component)
[0104] The raw material compounds of the catalyst precursor components are not particularly limited, and nitrates, carbonates, bicarbonates, acetates, ammonium salts, oxides, halides, oxyacids, oxyacid salts, etc. of the constituent elements of the catalyst precursor may be used alone or in combination of two or more.
[0105] Examples of the raw material compound of phosphorus include phosphoric acid, phosphorus pentoxide, and ammonium phosphate. Examples of the raw material compound of molybdenum include molybdenum oxides such as molybdenum trioxide, ammonium molybdates such as ammonium paramolybdate and ammonium dimolybdate, and molybdenum chloride. Examples of the raw material compound of vanadium include ammonium metavanadate, vanadium pentoxide, vanadium chloride, and vanadyl oxalate.
[0106] When a catalyst precursor containing copper in addition to phosphorus, molybdenum and vanadium is produced, examples of raw material compounds of copper include copper sulfate, copper nitrate, copper oxide, copper carbonate, copper acetate, copper chloride, etc. When a catalyst precursor containing G element in addition to phosphorus, molybdenum and vanadium is produced, examples of raw material compounds of G element include nitrates, carbonates, hydrogen carbonates, hydroxides, sulfates, acetates, chlorides, etc., and preferably carbonates or hydrogen carbonates are used.
[0107] The raw material compound of the catalyst precursor component may be used alone or in combination of two or more kinds for each element constituting the catalyst precursor component.
[0108] The total concentration of the raw material compounds of the catalyst precursor component in the A1 liquid is not particularly limited, but is preferably within a range of 5 to 90% by mass.
[0109] (Solvent)
[0110] Examples of the solvent include water, ethanol, and acetone. One or more of these may be used alone. Among these, water is preferably used from an industrial point of view.
[0111] (Preparation of A1 solution)
[0112] Liquid A1 is preferably prepared by adding the raw material compounds of the catalyst precursor components to a solvent in a preparation container and stirring while heating. In this way, a heteropoly acid suitable for producing an α,β-unsaturated carboxylic acid is sufficiently generated.
[0113] The heating temperature can be generally carried out in the range of 30 to 150° C., preferably in the range of 60 to 150° C. By setting the heating temperature to 60° C. or higher, the generation rate of the heteropoly acid can be sufficiently accelerated, and by setting it to 150° C. or lower, the evaporation of the solvent can be suppressed. The lower limit of the heating temperature is more preferably 80° C. or higher, and further preferably 90° C. or higher. In addition, the upper limit of the heating temperature is more preferably 130° C. or lower, and further preferably 110° C. or lower. In addition, it is also possible to concentrate or reflux during heating, or to heat the mixture under pressurized conditions by operating in a closed container, depending on the vapor pressure of the solvent used.
[0114] The heating rate is not particularly limited, but is preferably 0.8 to 15°C / min. By setting the heating rate to 0.8°C / min or more, the time required for step (i) can be shortened. In addition, by setting the heating rate to 15°C / min or less, a conventional heating device can be used for heating.
[0115] The stirring power is preferably 0.01 kW / m 3 The above is carried out, and more preferably 0.05 kW / m 3 By setting the stirring power to 0.01 kW / m 3 The above temperature, composition and local temperature variations of the A1 liquid are reduced, and a structure suitable for producing α, β-unsaturated carboxylic acids can be stably formed. In addition, from the perspective of the production cost of the catalyst precursor, stirring is usually preferably performed at 3.5 kW / m 3 The following stirring dynamics were used.
[0116] (Physical properties of A1 liquid)
[0117] The pH of the A1 solution is not particularly limited, but is preferably 0.1 to 4, more preferably 0.5 or more, and 3 or less. By making the pH of the A1 solution 0.1 or more, the step (ii) described later can be stably performed. In addition, by making the pH of the A1 solution 4 or less, a Keggin-type heteropoly acid suitable for producing an α,β-unsaturated carboxylic acid is stably generated. As a method for making the pH of the A1 solution 0.1 to 4, for example, methods such as using molybdenum trioxide as a molybdenum raw material, or appropriately selecting a raw material compound and adjusting the content of nitrate ions and oxalate ions can be cited. It should be noted that the pH can be measured using a pH meter such as D-21 (product name, manufactured by Horiba, Ltd.). In addition, whether a Keggin-type heteropolyacid is formed can be confirmed by infrared absorption analysis using NICOLET6700FT-IR (product name, manufactured by Thermo electron) and the like, and X-ray diffraction analysis using an X-ray diffraction device X'Pert PRO MPD (product name, manufactured by PANaltical) and the like.
[0118] <Step (ii)>
[0119] In step (ii), a raw material compound containing an ammonium group (compound B) is added to the liquid A1 obtained in step (i) to obtain a slurry (liquid A2) having a pH of 3 or less.
[0120] (Compound B)
[0121] Examples of compound B include ammonium hydrogen carbonate, ammonium carbonate, ammonium nitrate, aqueous ammonia, ammonium phosphate, and ammonium metavanadate. These may be used alone or in combination of two or more.
[0122] It should be noted that compound B can be dissolved or suspended in a solvent. As the solvent, for example, water, ethanol, acetone, etc. can be mentioned. They can be used alone or in combination of two or more. Among them, water is preferably used from an industrial point of view.
[0123] (Addition of Compound B)
[0124] The compound B is preferably added so as to satisfy the following formula (II).
[0125] v / M=0.10~1.80(II)
[0126] In formula (II), M is the molar number (mol) of molybdenum contained in the A1 solution, and v is the addition rate (mol / h) of ammonium ions.
[0127] Satisfying formula (II) means that the rate of addition of ammonium ions is slow enough. As a result, the supersaturation of the heteropolyacid ammonium salt generated by adding ammonium salt becomes smaller, so the particle size of the particles (primary particles) formed by the nucleus growth of the heteropolyacid ammonium salt becomes moderately larger. By drying the A2 liquid containing primary particles having such a particle size in the step (iii) described later, a catalyst precursor having a preferred median particle size can be easily obtained. In addition, the pores of the catalyst precursor come from the gaps between the primary particles generated in the A2 liquid, and the larger the particle size of the primary particles, the tendency of the primary particles to agglomerate in a manner that the gaps are smaller. Therefore, by drying the A2 liquid containing primary particles having the above-mentioned particle size in the step (iii) described later, a catalyst precursor having a specified pore volume can be easily obtained. v / M is more preferably 1.00h -1 Below, more preferably 0.50h -1 the following.
[0128] The temperature of the A1 liquid when compound B is added is preferably 90 to 99°C. If the temperature of the A1 liquid when compound B is added is high, the supersaturation of the heteropolyacid ammonium salt generated by adding the ammonium salt becomes smaller, so the particle size of the primary particles formed in the A2 liquid becomes larger, and the median particle size of the catalyst precursor generated when the A2 liquid is dried in the step (iii) described later also becomes larger. By adding the temperature of the A1 liquid in the above range, a catalyst precursor having a preferred median particle size can be easily obtained. In addition, the pores of the catalyst precursor come from the gaps between the primary particles generated in the A2 liquid, and the larger the particle size of the primary particles, the tendency of the primary particles to agglomerate in a manner that the gaps are smaller. Therefore, by drying the A2 liquid containing the primary particles having the above-mentioned particle size in the step (iii) described later, a catalyst precursor having a specified pore volume can be easily obtained. The lower limit of the temperature of A1 is more preferably above 92°C, and the upper limit is more preferably below 98°C.
[0129] When adding compound B, it is preferably added while stirring the A1 liquid at a rotation speed of 70 to 140 rpm. If the rotation speed is high, the A1 liquid is fully stirred, and the supersaturation of the heteropolyacid ammonium salt generated by adding the ammonium salt becomes smaller. As a result, the particle size of the primary particles formed in the A2 liquid becomes larger, and the median particle size of the catalyst precursor generated when the A2 liquid is dried in the step (iii) described later also becomes larger. In addition, the pores of the catalyst precursor come from the gaps between the primary particles generated in the A2 liquid. The larger the particle size of the primary particles, the more there is a tendency for the primary particles to agglomerate in a manner that the gaps are smaller, so the pore volume of the catalyst precursor becomes smaller. By stirring the A1 liquid at a rotation speed within the above range when adding compound B, a catalyst precursor having a specified pore volume and a preferred median particle size can be easily obtained. It is more preferred that the lower limit of the rotation speed is 100 rpm or more and the upper limit is 130 rpm or less. The A1 liquid can be stirred using a stirring device such as a rotary blade stirrer.
[0130] (Physical properties of A2 liquid)
[0131] The pH of the obtained A2 liquid is 3 or less, preferably the lower limit is 2 or more, and the upper limit is 2.8 or less. The pH of the A2 liquid is 3 or less, so that the Keggin type heteropoly acid suitable for manufacturing α, β-unsaturated carboxylic acid is stably generated. As a method for making the pH of the A2 liquid 3 or less, for example, molybdenum trioxide is used as a molybdenum raw material in the preparation of the A1 liquid, or the raw material compound is appropriately selected and the content of nitrate ions and oxalate ions is adjusted to adjust the pH of the A1 liquid, or the content of ammonium ions and cesium ions is adjusted in the preparation of the A2 liquid.
[0132] The solid content concentration of the obtained A2 liquid is preferably 30% by mass or less, more preferably 22 to 27% by mass. Thus, when the A2 liquid is dried in the step (iii) described later, the droplet shrinkage caused by the evaporation of the solvent can be appropriately generated, and a catalyst precursor having a preferred median particle size can be easily obtained. In addition, when the A2 liquid is dried in the step (iii), the part after the solvent evaporates from the droplet becomes the pores of the catalyst precursor. By making the solid content concentration of the A2 liquid within the above range, the solvent can be appropriately present in the A2 liquid, and a catalyst precursor having a specified pore volume can be easily obtained. It is further preferred that the lower limit of the solid content concentration of the A2 liquid is 23% by mass or more and the upper limit is 26.5% by mass or less.
[0133] The solid content concentration of the A2 liquid can be adjusted, for example, by the weight ratio of the raw material compound to the solvent used, the addition amount of the compound B and the compound containing the G element. If the addition amount of the compound B and the compound containing the G element is increased, the precipitation of the generated heteropolyacid salt is promoted, and the solid content concentration becomes larger. It should be noted that the solid content concentration of the A2 liquid refers to the value calculated by centrifuging the A2 liquid into a solution and a solid component, and measuring the mass of each, according to the following formula (III).
[0134] Solid content concentration (%) = solid content mass (g) / A2 liquid total mass (g) × 100 (III)
[0135] In the A2 liquid, when the total mass of the dissolved molybdenum element, phosphorus element and vanadium element relative to the total mass of the molybdenum element, phosphorus element and vanadium element is set to R, R is preferably 5 to 25% by mass, and more preferably 5 to 20% by mass. Thus, when the A2 liquid is dried in the step (iii) described later, the dissolved components precipitate in the gaps between the primary particles in the A2 liquid, thereby appropriately filling the gaps and easily obtaining a catalyst precursor having a predetermined pore volume. It is further preferred that the lower limit of R is 6% by mass or more and the upper limit is 15% by mass or less.
[0136] As a method for adjusting R, for example, there can be mentioned a method of changing the addition amount of compound B and the compound containing the G element, and the temperature of the A1 liquid when adding compound B. By increasing the addition amount of compound B and the compound containing the G element, the heteropolyacid salt generated increases, so R decreases. In addition, by increasing the temperature of the A1 liquid when adding compound B, the solubility of the heteropolyacid ammonium salt generated increases, so R increases. It should be noted that R is a value obtained by centrifuging the A2 liquid into a solution and a solid component and measuring the respective masses, and the result of analyzing the obtained solution and solid component by ICP emission spectrometry, and a value calculated by the following formula (IV).
[0137]
[0138] In formula (IV), m1 is the weight of the solution (g), m2 is the weight of the solid component (g), and M 1Mo is the concentration of molybdenum in the solution (mass %), M 1P is the concentration of phosphorus in the solution (mass %), M 1V is the concentration of vanadium in the solution (mass %), M 2Mo is the ratio of molybdenum in the solid content (mass %), M 2P is the ratio of phosphorus in the solid content (mass %), M 2V is the ratio (mass %) of vanadium in the solid content.
[0139] <Process (iii)>
[0140] In step (iii), the A2 liquid obtained in step (ii) is dried to obtain dry particles as a catalyst precursor. For drying, spray drying or drum drying can be mentioned, and spray drying is preferred. Spray drying can be performed using a spray dryer. Drum drying can be performed using a drum dryer.
[0141] In the spray dryer, the contact mode between the spray droplets and the hot air may be any of co-current, counter-current, and co-current and counter-current (mixed flow).
[0142] The inlet temperature of the spray dryer is preferably 100 to 500°C. The lower limit of the inlet temperature is more preferably 200°C or more, further preferably 220°C or more, and particularly preferably 240°C or more. In addition, the upper limit of the inlet temperature is more preferably 400°C or less, and further preferably 370°C or less. The outlet temperature of the spray dryer is preferably 100 to 200°C, and more preferably 105 to 200°C. For example, by increasing the inlet temperature and outlet temperature of the spray dryer, the evaporation of the solvent proceeds rapidly, so that the droplets are less likely to shrink during solvent evaporation, and there is a tendency for the pore volume and median particle size of the obtained catalyst precursor to become larger. By making the inlet temperature and outlet temperature of the spray dryer within the above range, a catalyst precursor having a specified pore volume and a preferred median particle size can be easily obtained.
[0143] The spray drying is preferably performed so that the water content of the obtained catalyst precursor is 0.1 to 4.5% by mass.
[0144] As described above, a catalyst precursor can be produced. The catalyst precursor may have catalytic activity, but from the viewpoint of the yield of the α,β-unsaturated carboxylic acid, it is preferred to use a catalyst produced by molding and / or calcining as described below.
[0145] [Method for producing catalyst]
[0146] The method for producing a catalyst of the present embodiment is a method for producing a catalyst used when producing an α,β-unsaturated carboxylic acid by oxidizing an α,β-unsaturated aldehyde, and the catalyst precursor of the present embodiment is molded and / or calcined. It should be noted that "molding and / or calcining" means that only molding can be performed, only calcination can be performed, or both molding and calcination can be performed.
[0147] <Molding of catalyst precursor>
[0148] The molding method of the catalyst precursor is not particularly limited, and known dry and wet molding methods can be applied, for example, tablet molding, compression molding, pressure molding, extrusion molding, granulation molding, etc. can be cited. The shape of the obtained molded body is not particularly limited, for example, cylindrical, annular, spherical and other shapes can be cited. In addition, during molding, it is preferred not to add a carrier to the catalyst precursor, and only the catalyst precursor is molded, and known additives such as graphite and talc can also be added as needed. It should be noted that when a carrier is used, the carrier is not particularly limited, and silicon dioxide can be preferably cited. In addition, molding can also be performed after calcination described later.
[0149] <Calcination of catalyst precursor>
[0150] The calcination can be carried out under the circulation of at least one of an oxygen-containing gas such as air and an inert gas, preferably under the circulation of an oxygen-containing gas such as air. Here, the inert gas refers to a gas that does not reduce the catalytic activity, and nitrogen, carbon dioxide, helium, argon, etc. can be mentioned. They can be used alone or in combination of two or more.
[0151] The calcination method is not particularly limited, and a fluidized bed, rotary kiln, muffle furnace, tunnel calcination furnace, etc. may be used. An appropriate method may be selected in consideration of the performance, mechanical strength, moldability, production efficiency, etc. of the final catalyst.
[0152] The calcination temperature (maximum temperature during calcination) is preferably 200 to 700°C, and more preferably the lower limit is 320°C or higher and the upper limit is 450°C or lower.
[0153] [Molded Catalyst Body]
[0154] The catalyst molded body of the present embodiment is a catalyst molded body used when oxidizing an α,β-unsaturated aldehyde to produce an α,β-unsaturated carboxylic acid, and contains a catalyst component containing phosphorus, molybdenum and vanadium. In addition, the pore volume of the above-mentioned catalyst molded body is 0.01 to 0.40 mL / g, and in the pore distribution curve of the above-mentioned catalyst molded body, when the height of the highest peak (peak A) having a vertex in the range of pore diameters of 0.05 to 10 μm is IA and the height of the second highest peak (peak B) is IB, IB / IA is 0.160 to 0.420.
[0155] So far, the pore volume and pore distribution of catalyst molded bodies for the production of α,β-unsaturated carboxylic acids have been studied separately. However, it is difficult to control them independently to produce catalyst molded bodies, and there has been no research on controlling both the pore volume and pore distribution of catalyst molded bodies. In addition, when the pore volume of the catalyst molded body is increased, the yield of α,β-unsaturated carboxylic acids is improved, but on the other hand, there is a problem that the weight of the catalyst molded body that can be filled into a reactor of a certain volume is reduced. Therefore, the effect of increasing the yield of α,β-unsaturated carboxylic acids brought about by increasing the pore volume of the catalyst molded body cannot be fully obtained.
[0156] In the present invention, the pore distribution of the catalyst molded body was studied and it was found that the above problems can be solved by setting the IB / IA ratio to a predetermined range. It was further found that by setting the pore volume of the catalyst molded body to a predetermined range, an α,β-unsaturated carboxylic acid can be produced at a particularly high yield.
[0157] <Composition of catalyst components>
[0158] The catalyst molded body of the present embodiment contains a catalyst component containing phosphorus, molybdenum and vanadium. From the viewpoint of improving the yield of α,β-unsaturated carboxylic acid, the preferred embodiment of the catalyst component is the same as the preferred embodiment of the catalyst precursor of the present embodiment for the ratio of the number of phosphorus atoms to the number of molybdenum atoms and the ratio of the number of vanadium atoms to the number of molybdenum atoms.
[0159] From the viewpoint of improving the yield of α, β-unsaturated carboxylic acid, the catalyst component is the same as the catalyst precursor of the present embodiment, and it is particularly preferred to have a composition represented by the above formula (I). It should be noted that the catalyst component may contain a small amount of elements not described in the above formula (I). For the composition represented by the above formula (I), the preferred mode of the catalyst component is the same as the preferred mode of the catalyst precursor of the present embodiment.
[0160] <Pore volume and pore distribution of catalyst molded body>
[0161] The pore volume of the catalyst molded body of the present embodiment is 0.01 to 0.40 mL / g. By making the pore volume 0.01 mL / g or more, the α,β-unsaturated aldehyde as a raw material can be fully diffused and fully act on the active sites on the surface, so the reaction rate is improved. In addition, the generated α,β-unsaturated carboxylic acid is also fully diffused, so the reaction of α,β-unsaturated carboxylic acid becoming a by-product due to gradual oxidation can be suppressed. By making the pore volume 0.4 mL / g or less, the density of the catalyst molded body becomes large enough, and the weight of the catalyst molded body that can be filled into a reactor of a certain volume increases, so the yield of α,β-unsaturated carboxylic acid is improved. The lower limit of the pore volume is preferably 0.10 mL / g or more, and more preferably 0.20 mL / g or more. The upper limit of the pore volume is preferably 0.35 mL / g or less, and more preferably 0.30 mL / g or less.
[0162] As a method for obtaining a catalyst molded body having a pore volume within the above-mentioned range, for example, there can be cited a method of manufacturing a catalyst molded body using the manufacturing method described later, and a method of adjusting the addition rate v (mol / h) of compound B, the temperature of liquid A1 and the stirring speed of liquid A1 in step (ii), a method of adjusting the physical properties of liquid A2, a method of adjusting the drying conditions in step (iii), and a method of adjusting the extrusion molding conditions in step (iv).
[0163] In the pore distribution curve of the catalyst molded body of the present embodiment, when the height of the highest peak (peak A) having a vertex in the range of pore diameter of 0.05 to 10 μm is defined as IA and the height of the second highest peak (peak B) is defined as IB, IB / IA is 0.160 to 0.420. The pore distribution satisfying this condition is particularly effective for the diffusion of the α,β-unsaturated aldehyde as a raw material and the generated α,β-unsaturated carboxylic acid, and can fully diffuse the α,β-unsaturated aldehyde and the α,β-unsaturated carboxylic acid regardless of the pore volume. As a result, the improvement of the yield of α,β-unsaturated carboxylic acid brought about by the sufficient diffusion of α,β-unsaturated aldehyde and α,β-unsaturated carboxylic acid and the improvement of the yield of α,β-unsaturated carboxylic acid brought about by the increase in the weight of the catalyst molded body that can be filled into a reactor of a certain volume can be achieved at the same time, and it is presumed that a good effect is obtained. The lower limit of IB / IA is preferably 0.200 or more, and the upper limit is preferably 0.400 or less.
[0164] The number of peaks having pore diameters in the range of 0.05 to 10 μm in the pore distribution curve is preferably 4 or less, more preferably 3 or less, and even more preferably 2 or less.
[0165] The apex of the peak A and the peak B is preferably present in a range of 0.05 μm or more, more preferably in a range of 0.08 μm or more, and further preferably in a range of 0.10 μm or more. In addition, it is preferably present in a range of 10 μm or less, more preferably in a range of 8 μm or less, and further preferably in a range of 6 μm or less. When the peak A and the peak B are in this range, a pore distribution suitable for diffusion of α, β-unsaturated aldehyde and α, β-unsaturated carboxylic acid is formed, and the yield of α, β-unsaturated carboxylic acid is improved.
[0166] It should be noted that in the present invention, the pore volume and pore distribution of the catalyst molded body are measured by mercury intrusion. The pore volume and pore distribution of the catalyst molded body can be measured by a pore distribution measuring device such as AutoPore IV-9500 (product name, made by Micromeritics). It should be noted that in the present invention, the pore size distribution curve refers to the logarithmic differential pore volume distribution curve. The logarithmic differential pore volume distribution refers to the value obtained by dividing the differential pore volume by the differential value of the common logarithm of the pore diameter and plotting it relative to the average pore diameter of each interval. In addition, in the present invention, the top of the peak refers to the position where the first-order derivative of the pore diameter distribution curve is 0 and the second-order derivative is negative. In addition, the height of the peak refers to the distance from the horizontal line with a value of 0 on the vertical axis to the top of the peak.
[0167] <Specific surface area of catalyst molded body>
[0168] The specific surface area of the catalyst molded body of this embodiment is preferably 1 to 10 m 2 / g. Through the specific surface area of 1m 2 / g or more, the number of active sites that can react with the α,β-unsaturated aldehyde as a raw material becomes sufficient, and the yield of α,β-unsaturated carboxylic acid is improved. 2 / g or less, the pore volume described later can be easily controlled within a predetermined range. The lower limit of the specific surface area is more preferably 1.5 m 2 / g or more, more preferably 2m 2 / g or more. In addition, the upper limit of the specific surface area is more preferably 8m 2 / g or less, more preferably 6m 2 / g or less, particularly preferably 4m 2 / g or less.
[0169] In the present invention, the specific surface area of the catalyst molded body is a value obtained by a nitrogen adsorption method. The specific surface area of the catalyst molded body can be calculated by a BET five-point method using, for example, Tristar 3000 (product name, manufactured by Micrometrics).
[0170] As a method for obtaining a catalyst molded body having a specific surface area within the above-mentioned range, for example, there can be cited a method of manufacturing a catalyst molded body using the manufacturing method described later and adjusting the addition rate v (mol / h) of compound B, the temperature of liquid A1 and the stirring speed of liquid A1 in step (ii), and a method of adjusting the physical properties of liquid A2.
[0171] <Shape of Catalyst Molded Body>
[0172] The shape of the catalyst molded body is not particularly limited, and any shape such as spherical, cylindrical, annular, star-shaped, and particles that are crushed and classified after molding can be cited. Among them, from the viewpoint of mechanical strength, spherical, cylindrical, and annular shapes are preferred. As the size of the molded object, it is not particularly limited. For example, in the case of a sphere, the diameter of the ball is preferably 0.1 to 10 mm. The lower limit of the diameter of the ball is more preferably 0.5 mm or more, more preferably 1 mm or more, and particularly preferably 3 mm or more. In addition, the upper limit of the diameter of the ball is more preferably 8 mm or less, and more preferably 6 mm or less. In the case of annular or cylindrical shapes, the diameter and height of the circle of the bottom surface of the ring or cylinder are preferably 0.1 to 10 mm. The lower limits of the diameter and height are more preferably 0.5 mm or more, more preferably 1 mm or more, and particularly preferably 3 mm or more. In addition, the upper limits of the diameter and height are more preferably 8 mm or less, and more preferably 6 mm or less. In the case of shapes other than this, the length between the two points farthest apart in the three-dimensional space of the catalyst molded body is preferably 0.1 to 10 mm. The lower limit of the length between the two points is more preferably 0.5 mm or more, more preferably 1 mm or more, and particularly preferably 3 mm or more. In addition, the upper limit of the length between the two points is more preferably 8 mm or less, and more preferably 6 mm or less. Thus, the yield of the target product and the continuous operation time of the catalyst molding are improved.
[0173] It should be noted that the catalyst molded body of the present embodiment is preferably an extruded molded body.
[0174] [Method for producing a molded catalyst body]
[0175] The catalyst molded body of the present embodiment contains catalyst components including phosphorus, molybdenum and vanadium, and has a pore volume of 0.01 to 0.40 mL / g. In the pore distribution curve, when the height of the highest peak (peak A) with a vertex in the pore diameter range of 0.05 to 10 μm is set to IA, and the height of the second highest peak (peak B) is set to IB, if IB / IA is 0.160 to 0.420, it can be manufactured according to a known method for manufacturing a catalyst molded body, preferably by the method for manufacturing a catalyst molded body of the present embodiment comprising the above-mentioned steps (i) to (iii) and the following step (iv).
[0176] Step (iv): Extrusion-molding the dried particles to obtain a catalyst molded body.
[0177] In addition, the method for producing the molded catalyst body of the present embodiment may further include a calcination step described later.
[0178] In the method for producing a molded catalyst according to the present embodiment, preferred aspects of steps (i) to (iii) are the same as preferred aspects of the method for producing a catalyst precursor according to the present embodiment.
[0179] In step (ii), satisfying formula (II) means that the addition rate of ammonium radical is sufficiently slow. Thus, the supersaturation of the heteropolyacid ammonium salt generated when the ammonium radical is added becomes smaller, so the particle size of the particles (primary particles) formed by the nucleus growth of the heteropolyacid ammonium salt becomes larger, and the strength of the dry particles generated when A2 is dried in step (iii) is improved.
[0180] Moreover, by extruding the dry particles with high strength in the step (iv) described later, the shape of the dry particles is maintained after molding. Therefore, in the catalyst molded body, two types of pores are formed, namely, pores in the dry particles derived from the gaps between the primary particles and pores derived from the gaps between the dry particles. Usually, the pores derived from the gaps between the dry particles are peak A, and the pores in the dry particles derived from the gaps between the primary particles are peak B. By adjusting the extrusion molding conditions of the step (iv) described later, the ratio of the pores in the dry particles derived from the gaps between the primary particles and the pores derived from the gaps between the dry particles can be adjusted, and the catalyst molded body with IB / IA within the specified range can be easily obtained.
[0181] In addition, if the particle size of the primary particles generated in the A2 liquid increases, the particle size of the dry particles also increases. At this time, when the dry particles are extruded in the step (iv) described later, the gaps between the primary particles and the gaps between the dry particles become pores, so the pore diameter of the peak in the pore distribution increases. By adding ammonium radicals in a manner that satisfies the above formula (II), a catalyst molded body in which the apexes of the above peaks A and B exist in a preferred range can be easily obtained.
[0182] In formula (II), v / M is more preferably 1.00h -1 Below, more preferably 0.50h -1 the following.
[0183] The temperature of the A1 liquid when adding the compound B is preferably 90 to 99°C. If the temperature of the A1 liquid when adding the compound B is low, the supersaturation of the heteropolyacid ammonium salt generated when the ammonium radical is added becomes larger, so the particle size of the primary particles formed in the A2 liquid becomes smaller, and the specific surface area of the catalyst molded body obtained in the step (iv) described later becomes larger. By setting the temperature of the A1 liquid when adding the compound B within the above range, a catalyst molded body having a preferred specific surface area can be easily obtained.
[0184] In addition, if the particle size of the primary particles generated in the A2 liquid becomes smaller, the particle size of the dry particles also becomes smaller. When the dry particles are molded, the gaps between the primary particles and the gaps between the dry particles become pores, so the pore diameter of the peak in the pore distribution becomes smaller. By setting the temperature of the A1 liquid when adding compound B to 90-99°C, it is easy to obtain a catalyst molded body in which the apexes of the peak A and peak B are present in a preferred range. More preferably, the lower limit of the temperature of A1 is 92°C or higher and the upper limit is 98°C or lower.
[0185] When adding compound B, it is preferably added while stirring A1 liquid at a rotation speed of 70 to 140 rpm. A1 liquid can be stirred using a stirring device such as a rotary blade stirrer. By stirring A1 liquid at a rotation speed of more than 70 rpm, A1 liquid is fully stirred, so the supersaturation of the heteropolyacid ammonium salt generated by adding ammonium salt becomes smaller. Thus, for the same reasons as above, the strength of the dry particles generated when A2 liquid is dried in step (iii) is improved, and a catalyst molded body with IB / IA within a specified range can be easily obtained. In addition, a catalyst molded body in which the vertices of the above-mentioned peaks A and B are present in a preferred range can be easily obtained.
[0186] In addition, by stirring the A1 solution at a rotation speed of 140 rpm or less, the supersaturation of the heteropolyacid ammonium salt generated when the ammonium radical is added becomes larger, so the particle size of the primary particles formed in the A2 solution becomes smaller. Thus, in the step (iv) described later, a catalyst molded body having a preferred specific surface area can be easily obtained.
[0187] More preferably, the lower limit of the rotation speed is 100 rpm or more and the upper limit is 130 rpm or less.
[0188] The solid content concentration of the obtained A2 liquid is preferably 30% by mass or less, more preferably 22 to 27% by mass. When the A2 liquid is dried in step (iii), the part where the solvent evaporates from the droplets becomes the pores of the dried particles. By making the solid content concentration of the A2 liquid within the above range, the solvent component is appropriately present in the A2 liquid, and dried particles with a suitable pore volume can be easily obtained. When the dried particles are molded, a catalyst molded body with a specified pore volume can be easily obtained. It is further preferred that the lower limit of the solid content concentration is 23% by mass or more and the upper limit is 26.5% by mass or less.
[0189] In the A2 liquid, when the total mass of the dissolved molybdenum element, phosphorus element and vanadium element relative to the total mass of the molybdenum element, phosphorus element and vanadium element is defined as R, R is preferably 5 to 25% by mass, and more preferably 5 to 20% by mass. Thus, when the A2 liquid is dried in step (iii), the dissolved components are precipitated in the gaps between the primary particles in the A2 liquid, so that the gaps can be appropriately filled, and dried particles with a suitable pore volume can be easily obtained. Moreover, by molding the dried particles, a catalyst molded body with a specified pore volume can be easily obtained.
[0190] In addition, since the strength is improved by filling the voids in the dry material particles, when the dry material particles are extruded and molded in the step (iv) described later, the shape of the dry material particles can be maintained even after molding. Therefore, two types of pores are formed in the catalyst molded body, namely, pores in the dry material particles originating from the voids between the primary particles and pores originating from the voids between the dry material particles. By adjusting the extrusion molding conditions of the step (iv) described later, the ratio of the pores in the dry material particles originating from the voids between the primary particles to the pores originating from the voids between the dry material particles can be adjusted, and a catalyst molded body within a specified range of IB / IA can be easily obtained.
[0191] The lower limit of R is more preferably 6 mass % or more, and the upper limit is more preferably 15 mass % or less.
[0192] In step (iii), when the drying is performed by spray drying using a spray dryer, the inlet temperature of the spray dryer is preferably 100 to 500°C. The lower limit of the inlet temperature is more preferably 200°C or more, further preferably 220°C or more, and particularly preferably 240°C or more. In addition, the upper limit of the inlet temperature is more preferably 400°C or less, and further preferably 370°C or less. The outlet temperature of the spray dryer is preferably 100 to 200°C, and more preferably 105 to 200°C. For example, by lowering the inlet temperature and outlet temperature of the spray dryer, the evaporation of the solvent proceeds slowly, so that the droplets tend to shrink when the solvent evaporates, and there is a tendency that the pore volume of the obtained dried particles becomes smaller and the pore volume of the catalyst molded body also becomes smaller. By setting the inlet temperature and outlet temperature of the spray dryer within the above range, dried particles having a specified pore volume can be easily obtained.
[0193] In addition, by making the inlet temperature and outlet temperature of the spray dryer above the above temperature, the strength of the dried particles is improved, so when the dried particles are extruded in the step (iv) described later, the shape of the dried particles is maintained even after molding. Therefore, in the catalyst molded body, two types of pores are formed, namely, pores in the dried particles that originate from the gaps between the primary particles and pores that originate from the gaps between the dried particles. By adjusting the extrusion molding conditions of the step (iv) described later, the ratio of the pores in the dried particles that originate from the gaps between the primary particles and the pores that originate from the gaps between the dried particles can be adjusted, and the catalyst molded body can be easily obtained in which IB / IA is within the specified range.
[0194] The spray drying is preferably performed so that the moisture content of the obtained dry particles is 0.1 to 4.5% by mass.
[0195] <Step (iv)>
[0196] In step (iv), the dried particles obtained in step (iii) are extruded to obtain a catalyst molded body. It should be noted that the extrusion molding may be performed after the calcination step described below.
[0197] By molding the dried particles by extrusion molding, a catalyst molded body having a predetermined pore volume and pore distribution can be easily obtained. When a carrier is used, the carrier is not particularly limited, but preferably, silica is used.
[0198] In the extrusion molding, the dry particles can be crushed as needed and then extrusion molding can be performed. In addition, according to the properties of the dry particles, an additive can be mixed in the dry particles to obtain a kneaded product, and an extruder can be used to perform extrusion molding. Preferably, a liquid and an additive are mixed in the dry particles to obtain a kneaded product, and an extruder is used to perform extrusion molding. More preferably, a liquid and a binder are mixed in the dry particles to obtain a kneaded product, and an extruder is used to perform extrusion molding.
[0199] (liquid mixed with dry particles)
[0200] The liquid mixed with the dry particles is not particularly limited as long as it has the function of wetting the dry particles, and examples thereof include water, methanol, ethanol, propanol, butanol and other alcohols having 1 to 4 carbon atoms. Among them, ethanol and propanol are preferred from the viewpoint that the dry particles do not disintegrate and pores effective for the oxidation reaction of α,β-unsaturated aldehydes are easily formed. These may be used alone or in combination of two or more.
[0201] The amount of liquid used is appropriately selected according to the type, size, type of liquid, etc. of the dry particles, and is preferably 15 to 60 parts by mass relative to 100 parts by mass of the dry particles. If the amount of liquid used is increased, the dry particles are not easy to disintegrate during extrusion molding, and the pores from the gaps between the dry particles become more, so there is a tendency for IB / IA to become smaller. By making the amount of liquid used relative to 100 parts by mass of the dry particles 15 parts by mass or more, it is easy to obtain a catalyst molded body with IB / IA within a specified range. In addition, by making the amount of liquid used less than 60 parts by mass, it is easy to obtain a catalyst molded body with a small total pore volume and high strength. The lower limit of the amount of liquid used relative to 100 parts by mass of the dry particles is more preferably more than 16 parts by mass. In addition, the upper limit is more preferably less than 50 parts by mass, further preferably less than 45 parts by mass, and particularly preferably less than 35 parts by mass.
[0202] (Additives to be mixed with dry material particles)
[0203] The additives mixed with the dry particles are not particularly limited, and for example, known additives such as graphite, talc, organic binders, and inorganic binders can be used. Among them, from the viewpoint of improving the formability in extrusion molding, it is preferred to mix an organic binder. As the organic binder, for example, high molecular compounds such as polyvinyl alcohol, α-glucan derivatives, β-glucan derivatives, etc. can be cited. They can be used only one, or two or more can be used in combination.
[0204] The above-mentioned α-glucan derivative is a substance formed by bonding glucose in an α-type structure in a polysaccharide composed of glucose. For example, derivatives such as α1-4 glucan, α1-6 glucan, and α1-4 / 1-6 glucan can be mentioned. As such α-glucan derivatives, amylose, glycogen, amylopectin, pullulan, dextrin, cyclodextrin, etc. can be mentioned. They can be used alone or in combination of two or more.
[0205] The above-mentioned β-glucan derivatives are substances formed by bonding glucose in a β-type structure in a polysaccharide composed of glucose. For example, derivatives such as β1-4 glucan, β1-3 glucan, β1-6 glucan, and β1-3 / 1-6 glucan can be cited. As such β-glucan derivatives, for example, cellulose derivatives such as methylcellulose, ethylcellulose, carboxymethylcellulose, sodium carboxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, hydroxyethylmethylcellulose, hydroxybutylmethylcellulose, and ethylhydroxyethylcellulose, curdlan, laminarin, paramylon, callose, lipstick, and scleroglucan can be cited. They can be used alone or in combination of two or more.
[0206] The organic binder may be used in an unpurified state or after purification. However, if it contains metals or residual components after strong heating as impurities, the catalyst performance may be reduced, so it is preferable to reduce the content of these components to a smaller extent.
[0207] The amount of the organic binder used is appropriately selected according to the type, size, type of liquid, etc. of the dry particles, preferably 0.05 to 15 parts by mass, with respect to 100 parts by mass of the dry particles, and more preferably the lower limit is 0.1 parts by mass or more, and the upper limit is 10 parts by mass or less. By using an organic binder in an amount of 0.05 parts by mass or more, the moldability of extrusion molding is improved. In addition, by performing the calcination process described later, the part where the organic binder is removed becomes pores, and a catalyst molded body with a specified pore volume can be easily obtained. In addition, by making the amount of the organic binder used less than 15 parts by mass, the organic binder can be easily removed by performing the calcination process described later, so that the adverse effects on the catalyst performance can be suppressed.
[0208] (mixing of dry particles with liquid and additives)
[0209] The mixing of the dry material particles with the liquid and the additives is preferably carried out by using an intermittent mixer with a double-arm type stirring blade, a continuous mixer such as a shaft rotating reciprocating type or a self-cleaning type, etc. As a mixer, an intermittent mixer is preferred from the viewpoint that the mixing state can be confirmed. It should be noted that the end point of mixing is the moment when the mixing is mixed to a state that can be extruded, and the end point is judged by visual inspection or feel.
[0210] (Extrusion molding)
[0211] Extrusion molding is performed by placing the dried particles or mixture into a mold and applying pressure to extrude the mixture, thereby molding the mixture into a certain shape to obtain an extruded body. Extrusion molding can be performed using, for example, a screw extruder, a plunger extruder, etc., preferably a plunger extruder.
[0212] The extrusion pressure is preferably 0.1 to 30 MPa. By having an extrusion pressure of 0.1 MPa or more, a catalyst molded body having a specified pore volume and high mechanical strength can be stably obtained. In addition, if the extrusion pressure is small, the destruction of the dry particles constituting the catalyst molded body is suppressed, and the pores from the gaps between the dry particles become more, so there is a tendency for IB / IA to become smaller. By having an extrusion pressure of 30 MPa or less, a catalyst molded body with IB / IA within a specified range can be easily obtained. The lower limit of the extrusion pressure is more preferably 0.5 MPa or more, more preferably 1 MPa or more, and particularly preferably 2 MPa or more. In addition, the upper limit of the extrusion pressure is more preferably 20 MPa or less, and more preferably 15 MPa or less.
[0213] The obtained catalyst molded body can be cut into a desired size as required. The cutting method can be selected from any known method, for example, a method using a rotating cutting blade, a method using a reciprocating cutting blade, etc.
[0214] When the dry particles are mixed with a liquid and extruded, it is preferred to keep the catalyst molded body obtained as needed at a temperature of 10 to 200°C to remove the liquid contained in the catalyst molded body. By making the temperature above 10°C, the liquid component can be fully removed. In addition, by making the temperature below 200°C, the deterioration of the catalyst molded body can be prevented. The lower limit of the temperature is more preferably above 20°C. In addition, the upper limit of the temperature is more preferably below 180°C, further preferably below 150°C, and particularly preferably below 120°C. It should be noted that the liquid can also be removed by drying the catalyst molded body using any commonly known dryer. The operating conditions of the dryer are not particularly limited, and for example, it can be kept in an air atmosphere or a nitrogen atmosphere.
[0215] The catalyst molded body obtained in step (iv) exhibits catalytic performance and can be used to produce α,β-unsaturated carboxylic acids. It is easy to obtain a catalyst molded body having a predetermined specific surface area, pore volume and pore distribution curve by further calcining as described below, and the yield of α,β-unsaturated carboxylic acids is improved, which is preferred. In the present invention, the calcined products including these calcined products are collectively referred to as catalyst molded bodies.
[0216] <Calcination process>
[0217] In the calcination step, the dried particles obtained in the step (iii) or the catalyst molded body obtained in the step (iv) are calcined as necessary.
[0218] The calcination can be carried out under the circulation of at least one of an oxygen-containing gas such as air and an inert gas, preferably under the circulation of an oxygen-containing gas such as air. Here, the inert gas refers to a gas that does not reduce the catalytic activity, and nitrogen, carbon dioxide, helium, argon, etc. can be mentioned. They can be used alone or in combination of two or more.
[0219] The calcination method is not particularly limited, and fluidized bed, rotary kiln, muffle furnace, tunnel calcination furnace, etc. may be selected. An appropriate method may be selected in consideration of the performance, mechanical strength, moldability, production efficiency, etc. of the final catalyst.
[0220] The calcination temperature (maximum temperature during calcination) is preferably 200 to 700°C, and more preferably the lower limit is 320°C or higher and the upper limit is 450°C or lower.
[0221] As described above, a shaped catalyst body can be produced.
[0222] [Method for producing α,β-unsaturated carboxylic acid]
[0223] In the method for producing an α,β-unsaturated carboxylic acid of the present embodiment, an α,β-unsaturated aldehyde is oxidized using a catalyst obtained by molding and / or calcining a catalyst precursor of the present embodiment or a catalyst molded body of the present embodiment. In addition, in the method for producing an α,β-unsaturated carboxylic acid of the present embodiment, an α,β-unsaturated aldehyde is oxidized using a catalyst obtained by molding and / or calcining a catalyst precursor manufactured by the method for producing a catalyst precursor of the present embodiment or a catalyst molded body manufactured by the method for producing a catalyst molded body of the present embodiment. According to these methods, unsaturated carboxylic acids can be produced in high yield. From the viewpoint of the yield of the product, the α,β-unsaturated aldehyde and the α,β-unsaturated carboxylic acid are preferably methacrolein and methacrylic acid, respectively.
[0224] The method for producing an α,β-unsaturated carboxylic acid of the present embodiment can be carried out by contacting a catalyst obtained by molding and / or calcining a catalyst precursor of the present embodiment, or a catalyst molding, with a raw material gas containing an α,β-unsaturated aldehyde. A fixed bed reactor can be used for this reaction.
[0225] The reaction can be carried out by filling a reactor with a catalyst or a catalyst molded body and supplying a raw material gas to the reactor. The catalyst layer or the catalyst molded body layer can be a single layer, or multiple catalysts or catalyst molded bodies with different activities can be divided into multiple layers for filling. In addition, in order to control the activity, the catalyst or the catalyst molded body can be diluted with an inactive carrier for filling.
[0226] The concentration of α,β-unsaturated aldehyde in the raw material gas is preferably 1 to 20% by volume, more preferably 3% by volume or more and 10% by volume or less. The α,β-unsaturated aldehyde as the raw material may contain a small amount of impurities such as lower saturated aldehydes that do not substantially affect the reaction.
[0227] The oxygen source of the raw material gas is not particularly limited, and the use of air is industrially advantageous. In addition, a gas obtained by mixing pure oxygen in air or the like may be used as required. The proportion of oxygen in the raw material gas is not particularly limited, but is preferably 0.4 to 4 moles relative to 1 mole of the α,β-unsaturated aldehyde, and more preferably has a lower limit of 0.5 moles or more and an upper limit of 3 moles or less.
[0228] From an economic point of view, the raw gas can be diluted with an inert gas such as nitrogen and carbon dioxide. Furthermore, water vapor can also be added to the raw gas. By reacting in the presence of water vapor, α,β-unsaturated carboxylic acid can be obtained with a higher yield. The concentration of water vapor in the raw gas is preferably 0.1 to 50% by volume, and more preferably the lower limit is 1% by volume or more and the upper limit is 40% by volume.
[0229] The contact time between the raw gas and the catalyst or the catalyst molded body for producing α,β-unsaturated carboxylic acid is preferably 0.5 to 15 seconds, and more preferably the lower limit is 1.5 seconds or more and the upper limit is 10 seconds or less. The reaction pressure is preferably 0 to 1 MPaG. Here, "G" represents the gauge pressure, and 0 MPaG represents that the reaction pressure is atmospheric pressure. The reaction temperature is preferably 200 to 450°C, and more preferably the lower limit is 250°C or more and the upper limit is 400°C or less.
[0230] [Method for producing α,β-unsaturated carboxylic acid ester]
[0231] In the method for producing an α,β-unsaturated carboxylic acid ester of the present embodiment, the α,β-unsaturated carboxylic acid produced by the method for producing an α,β-unsaturated carboxylic acid ester of the present embodiment is esterified. That is, the method for producing an α,β-unsaturated carboxylic acid ester of the present embodiment includes: a step of producing an α,β-unsaturated carboxylic acid by the method of the present embodiment, and a step of esterifying the α,β-unsaturated carboxylic acid.
[0232] The alcohol to be reacted with the α,β-unsaturated carboxylic acid is not particularly limited, and examples thereof include methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, and the like. Examples of the obtained α,β-unsaturated carboxylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, and isobutyl (meth)acrylate. The esterification reaction may be carried out in the presence of an acidic catalyst such as a sulfonic acid type cation exchange resin. The temperature in the esterification reaction is preferably 50 to 200°C.
[0233] Example
[0234] Hereinafter, the present invention will be specifically described using Examples and Comparative Examples, but the present invention is not limited to these Examples. It should be noted that "parts" means "parts by mass".
[0235] (Composition ratio of catalyst precursor and composition ratio of catalyst component)
[0236] The molar ratio of each component is determined by analyzing the components of a catalyst precursor or a catalyst molded body dissolved in aqueous ammonia using an ICP emission spectrometer Optima 8300 ICP-OES Spectrometer (product name, manufactured by PerkinElmer). In addition, the molar ratio of ammonium radicals is determined by analyzing the catalyst precursor or the catalyst molded body using the Kjeldahl method.
[0237] (Specific surface area of catalyst molded body)
[0238] The specific surface area of the catalyst molded body was measured using a nitrogen adsorption measuring apparatus Tristar 3000 (product name, manufactured by Micrometrics Corporation) using 1.5 g of the catalyst molded body pretreated at 200° C., and was calculated by the BET five-point method.
[0239] (Pore volume of catalyst precursor)
[0240] The pore volume of the catalyst precursor was measured using a mercury intrusion pore distribution measuring apparatus AutoPore IV-9500 (product name, manufactured by Micrometrics Corporation) under the following conditions and calculated from the pore volume of pores having a pore diameter of 0.5 μm or less.
[0241] Determination sample amount: 1.5g
[0242] Sample pretreatment: heating at 90°C for 12 hours
[0243] Sample cell volume: 1.131mL
[0244] Initial vacuum: 5 minutes at 50 μmHg
[0245] Equilibration time: 5 minutes
[0246] Measuring pressure range: 0.0038~207MPa
[0247] Measuring pore diameter range: 0.006~329μm
[0248] (Pore Volume and Pore Distribution of Catalyst Molded Body)
[0249] The pore volume and pore distribution of the catalyst molded body were measured under the following conditions using a mercury intrusion pore distribution measuring apparatus AutoPore IV-9500 (product name, manufactured by Micrometrics Corporation).
[0250] Test sample: 10 catalyst molded bodies
[0251] Sample cell volume: 1.131mL
[0252] Initial vacuum: 5 minutes at 50 μmHg
[0253] Equilibration time: 5 minutes
[0254] Measuring pressure range: 0.0038~207MPa
[0255] Measuring pore diameter range: 0.006~329μm
[0256] In addition, the physical property values of mercury used in the measurement using the mercury intrusion pore distribution measuring device are as follows.
[0257] Mercury contact angle: 130°
[0258] Mercury surface tension: 485 dynes / cm
[0259] Mercury density: 13.5335 g / mL
[0260] (Median particle size of catalyst precursor)
[0261] The median particle size of the catalyst precursor was measured under the following conditions using a laser diffraction wet particle size distribution analyzer LA-700 (product name, manufactured by Horiba, Ltd.).
[0262] Dispersion medium: ethanol
[0263] Refractive index setting: 1.8
[0264] (Analysis of Keggin-type heteropolyacid in catalyst precursor)
[0265] The presence or absence of Keggin-type heteropolyacid in the catalyst precursor is determined by infrared absorption analysis using NICOLET6700FT-IR (product name, manufactured by Thermo Electron). FT-IR measurement is performed using a transmission method. First, KBr is formed into granules using a tablet forming machine, and background measurement is performed. Next, KBr is diluted and mixed in a manner such that the concentration of the catalyst is 0.5 to 1% by mass, and the mixture is similarly formed into granules for measurement. For the infrared absorption spectrum obtained, the vertical axis is absorbance, the horizontal axis is wave number, and baseline correction is performed in the horizontal direction so that 1200 cm -1 The absorbance under 0 is known to be 0. It is known that in the Keggin structure, four characteristic peaks can be observed, which are attributed to the vibration of PO, MO, MOM between octahedrons, and MOM (M = Mo, V, etc.) within the octahedron. -1 、965cm -1 、870cm -1 、790cm -1 When all of these peaks are observed in the obtained infrared absorption spectrum, it is judged that the compound has a Keggin structure.
[0266] (Analysis of raw gas and products)
[0267] The raw material gas and the product were analyzed using a gas chromatograph (apparatus: GC-2014 manufactured by Shimadzu Corporation, column: DB-FFAP manufactured by J&W, 30 m×0.32 mm, film thickness 1.0 μm). The yield of the generated methacrylic acid was calculated by the following formula.
[0268] Yield of methacrylic acid (%) = (N2 / N1) × 100
[0269] Here, N1 is the number of moles of methacrolein supplied, and N2 is the number of moles of methacrylic acid produced.
[0270] [Catalyst precursor]
[0271] <Example 1-1>
[0272] 400 parts of pure water at 25°C was used as a solvent, and 100 parts of molybdenum trioxide, 7.5 parts of ammonium metavanadate, 11.4 parts of an 85 mass % phosphoric acid aqueous solution, and 7.0 parts of copper (II) nitrate trihydrate were added. The obtained slurry was heated to 95°C while stirring, and the liquid temperature was maintained at 95°C and stirred for 3 hours. Next, while the liquid temperature was maintained at 95°C and stirred, a solution in which 15.7 parts of cesium bicarbonate was dissolved in 20 parts of pure water was mixed and stirred for 15 minutes to obtain A1 liquid.
[0273] Next, the temperature of the A1 liquid was maintained at 95°C, and a solution of 15.0 parts of ammonium carbonate dissolved in 20 parts of pure water was added while stirring at 110 rpm using a rotary blade stirrer. The addition required 105.7 minutes. The temperature and v / M of the A1 liquid at this time are shown in Table 1. After the addition was completed, the liquid temperature was further maintained at 95°C and stirred for 15 minutes to obtain the A2 liquid. The pH, solid content concentration and R of the A2 liquid are shown in Table 1.
[0274] The obtained A2 liquid was spray dried at a dryer inlet temperature of 300°C to obtain a catalyst precursor. The element composition of the catalyst precursor other than oxygen was Mo 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 (NH4) 5.7 In addition, the catalyst precursor contained a Keggin-type heteropoly acid. Table 1 shows the pore volume, median particle size and bulk density of the catalyst precursor.
[0275] 100 parts of the obtained catalyst precursor were mixed with 5 parts of hydroxypropyl cellulose, 4 parts of pure water and 16 parts of ethanol, and kneaded until it became clay-like to obtain a mixture. The mixture was extruded at an extrusion pressure of 10 MPa using an extruder to form a cylindrical shape with a diameter of 5.5 mm and a height of 5 mm, and dried at 25° C. for 12 hours under air circulation to obtain a molded body.
[0276] The obtained molded body was calcined at 380° C. for 2 hours in an air atmosphere to obtain a catalyst.
[0277] The obtained catalyst was filled in a reaction tube to form a catalyst layer, and an oxidation reaction of methacrolein was carried out under the following conditions. The results are shown in Table 1.
[0278] Raw gas composition: 5 vol% methacrolein, 10 vol% oxygen, 30 vol% water vapor and 55 vol% nitrogen
[0279] Reaction temperature: 285℃
[0280] Contact time between raw gas and catalyst: 3.6 seconds
[0281] <Example 1-2>
[0282] Liquid A1 was obtained by the same method as in Example 1-1.
[0283] Next, the temperature of the A1 liquid was maintained at 95°C, and a solution of 12.3 parts of ammonium carbonate dissolved in 20 parts of pure water was added while stirring at 110 rpm using a rotary blade stirrer. The addition required 86.6 minutes. The temperature and v / M of the A1 liquid at this time are shown in Table 1. After the addition was completed, the liquid temperature was further maintained at 95°C and stirred for 15 minutes to obtain the A2 liquid. The pH, solid content concentration and R of the A2 liquid are shown in Table 1.
[0284] The obtained A2 liquid was dried in the same manner as in Example 1-1 to obtain a catalyst precursor. The element composition of the catalyst precursor other than oxygen was Mo 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 (NH4) 4.9 In addition, the catalyst precursor contained a Keggin-type heteropoly acid. Table 1 shows the pore volume, median particle size and bulk density of the catalyst precursor.
[0285] The obtained catalyst precursor was used to perform molding and calcination in the same manner as in Example 1-1.
[0286] The obtained catalyst was filled in a reaction tube to form a catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 1-1. The results are shown in Table 1.
[0287] <Example 1-3>
[0288] Liquid A2 was obtained by the same method as in Example 1-1.
[0289] The obtained A2 liquid was dried in the same manner as in Example 1-1, and sieved using a sieve with a mesh size of 15 μm, and the dried product falling under the sieve was used as a catalyst precursor. The element composition of the catalyst precursor other than oxygen was Mo 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 (NH4) 5.7 In addition, the catalyst precursor contained a Keggin-type heteropoly acid. Table 1 shows the pore volume, median particle size and bulk density of the catalyst precursor.
[0290] The obtained catalyst precursor was used to perform molding and calcination in the same manner as in Example 1-1.
[0291] The obtained catalyst was filled in a reaction tube to form a catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 1-1. The results are shown in Table 1.
[0292] <Example 1-4>
[0293] Liquid A1 was obtained by the same method as in Example 1-1 except that 13.5 parts of cesium carbonate was used instead of 15.7 parts of cesium hydrogen carbonate.
[0294] Next, using this A1 solution, A2 solution was obtained by the same method as in Example 1-1. Table 1 shows the pH, solid content concentration, and R of this A2 solution.
[0295] The obtained A2 liquid was spray dried at a dryer inlet temperature of 250°C to obtain a catalyst precursor. The element composition of the catalyst precursor other than oxygen was Mo 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 (NH4) 5.7 In addition, the catalyst precursor contained a Keggin-type heteropoly acid. Table 1 shows the pore volume, median particle size and bulk density of the catalyst precursor.
[0296] The obtained catalyst precursor was used to perform molding and calcination in the same manner as in Example 1-1.
[0297] The obtained catalyst was filled in a reaction tube to form a catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 1-1. The results are shown in Table 1.
[0298] <Example 1-5>
[0299] Liquid A1 was obtained by the same method as in Example 1-1.
[0300] Next, a solution prepared by dissolving 15.0 parts of ammonium carbonate in 20 parts of pure water was added over 21.2 minutes to obtain a liquid A2. The v / M at this time, the pH, the solid content concentration and R of the liquid A2 are shown in Table 1.
[0301] The obtained A2 liquid was dried in the same manner as in Example 1-1 to obtain a catalyst precursor. The element composition of the catalyst precursor other than oxygen was Mo 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 (NH4) 1.9 In addition, the catalyst precursor contained a Keggin-type heteropoly acid. Table 1 shows the pore volume, median particle size and bulk density of the catalyst precursor.
[0302] The obtained catalyst precursor was used to perform molding and calcination in the same manner as in Example 1-1.
[0303] The obtained catalyst was filled in a reaction tube to form a catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 1-1. The results are shown in Table 1.
[0304] <Comparative Example 1-1>
[0305] 400 parts of pure water at 25°C was used as a solvent, and 100 parts of molybdenum trioxide, 7.5 parts of ammonium metavanadate, and 7.0 parts of copper (II) nitrate trihydrate were added. The obtained slurry was heated to 95°C while stirring, and the liquid temperature was maintained at 95°C and stirred for 3 hours. Then, the liquid temperature was lowered to 50°C, and a solution of 15.7 parts of cesium bicarbonate dissolved in 20 parts of pure water was mixed and stirred for 15 minutes while the liquid temperature was maintained at 50°C and stirred, to obtain A1' liquid.
[0306] Next, the temperature of the A1' liquid was maintained at 50°C, and a solution of 15.8 parts of ammonium nitrate dissolved in 20 parts of pure water was added while stirring at 110 rpm using a rotary blade stirrer. The addition took 6.8 minutes. The temperature and v / M of the A1' liquid at this time are shown in Table 1. After the addition was completed, the liquid temperature was further maintained at 95°C and stirred for 15 minutes. 11.4 parts of an 85% by mass phosphoric acid aqueous solution was mixed with the obtained slurry and stirred for 15 minutes to obtain an A2' liquid. The pH, solid content concentration and R of the A2' liquid are shown in Table 1.
[0307] The obtained A2' liquid was dried in the same manner as in Example 1-1 to obtain a catalyst precursor. The element composition of the catalyst precursor other than oxygen was Mo 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 (NH4) 4.5 In addition, the catalyst precursor contained a Keggin-type heteropoly acid. Table 1 shows the pore volume, median particle size and bulk density of the catalyst precursor.
[0308] The obtained catalyst precursor was used to perform molding and calcination in the same manner as in Example 1-1.
[0309] The obtained catalyst was filled in a reaction tube to form a catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 1-1. The results are shown in Table 1.
[0310] <Comparative Example 1-2>
[0311] Liquid A1' was obtained by the same method as in Comparative Example 1-1 except that 200 parts of pure water at 25° C. was used as the solvent.
[0312] Next, using this A1′ liquid, A2′ liquid was obtained by the same method as in Comparative Example 1-1. Table 1 shows the pH, solid content concentration, and R of this A2′ liquid.
[0313] The obtained A2' liquid was dried in the same manner as in Example 1-1 to obtain a catalyst precursor. The element composition of the catalyst precursor other than oxygen was Mo 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 (NH4) 4.5 In addition, the catalyst precursor contained a Keggin-type heteropoly acid. Table 1 shows the pore volume, median particle size and bulk density of the catalyst precursor.
[0314] The obtained catalyst precursor was used to perform molding and calcination in the same manner as in Example 1-1.
[0315] The obtained catalyst was filled in a reaction tube to form a catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 1-1. The results are shown in Table 1.
[0316] <Comparative Examples 1-3>
[0317] Liquid A1 was obtained by the same method as in Example 1-1.
[0318] Next, liquid A2' was obtained in the same manner as in Example 1-1 except that a solution of 15.0 parts of ammonium carbonate dissolved in 20 parts of pure water was added over 184.0 minutes. Table 1 shows v / M at this time, pH, solid content concentration and R of the liquid A2'.
[0319] The obtained A2' liquid was dried in the same manner as in Example 1-1 to obtain a catalyst precursor. The element composition of the catalyst precursor other than oxygen was Mo 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 (NH4) 2.0 In addition, the catalyst precursor contained a Keggin-type heteropoly acid. Table 1 shows the pore volume, median particle size and bulk density of the catalyst precursor.
[0320] The obtained catalyst precursor was used to perform molding and calcination in the same manner as in Example 1-1.
[0321] The obtained catalyst was filled in a reaction tube to form a catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 1-1. The results are shown in Table 1.
[0322]
[0323] As shown in Table 1, Examples 1-1 to 1-5 using catalyst precursors having pore volumes within a predetermined range showed higher methacrylic acid yields than the comparative examples.
[0324] In addition, methacrylic acid ester can be obtained by esterifying the methacrylic acid obtained in Examples 1-1 to 1-5.
[0325] [Molded Catalyst Body]
[0326] <Example 2-1>
[0327] 400 parts of pure water at 25°C was used as a solvent, and 100 parts of molybdenum trioxide, 7.5 parts of ammonium metavanadate, 11.4 parts of an 85 mass % phosphoric acid aqueous solution, and 7.0 parts of copper (II) nitrate trihydrate were added. The obtained slurry was heated to 95°C while stirring, and the liquid temperature was maintained at 95°C and stirred for 3 hours. Next, while the liquid temperature was maintained at 95°C and stirred, a solution in which 15.7 parts of cesium bicarbonate was dissolved in 20 parts of pure water was mixed and stirred for 15 minutes to obtain A1 liquid.
[0328] Next, the temperature of the A1 liquid was maintained at 95°C, and a solution of 15.0 parts of ammonium carbonate dissolved in 20 parts of pure water was added while stirring at 110 rpm using a rotary blade stirrer. The addition required 105.7 minutes. The temperature and v / M of the A1 liquid at this time are shown in Table 2. After the addition was completed, the liquid temperature was further maintained at 95°C and stirred for 15 minutes to obtain the A2 liquid. The pH, solid content concentration and R of the A2 liquid are shown in Table 2.
[0329] The obtained A2 liquid was spray-dried at a dryer inlet temperature of 300° C. to obtain dry particles.
[0330] Next, 5 parts of hydroxypropyl cellulose, 4 parts of pure water and 16 parts of ethanol were mixed with 100 parts of the obtained dry particles, and kneaded until it became clay-like to obtain a mixture. The mixture was extruded using an extrusion molding machine at an extrusion pressure of 10 MPa and molded into a cylindrical shape with a diameter of 5.5 mm and a height of 5 mm. It was dried at 25°C for 12 hours under air circulation, and then calcined at 380°C for 2 hours in an air atmosphere to obtain a catalyst molded body. The element composition of the catalyst molded body other than oxygen is Mo: 12 P 1.7 V 1.1 Cu 0.5 Cs1.4 , the molar ratio of ammonium radical is 1 or less. In addition, there are two peaks in the range of pore diameter 0.05 to 10 μm in the pore distribution curve. The specific surface area, pore volume and IB / IA in the pore distribution curve of the catalyst molded body are shown in Table 2.
[0331] Next, the obtained molded catalyst was filled in a reaction tube to form a molded catalyst layer, and an oxidation reaction of methacrolein was carried out under the following conditions.
[0332] Raw gas composition: 5 vol% methacrolein, 10 vol% oxygen, 30 vol% water vapor and 55 vol% nitrogen
[0333] Reaction temperature: 285℃
[0334] Contact time between raw gas and catalyst molded body: 3.6 seconds
[0335] <Example 2-2>
[0336] Liquid A1 was obtained by the same method as in Example 2-1.
[0337] Next, the temperature of the A1 liquid was maintained at 95°C, and a solution of 12.3 parts of ammonium carbonate dissolved in 20 parts of pure water was added while stirring at 110 rpm using a rotary blade stirrer. The addition required 86.6 minutes. The temperature and v / M of the A1 liquid at this time are shown in Table 2. After the addition was completed, the liquid temperature was further maintained at 95°C and stirred for 15 minutes to obtain the A2 liquid. The pH, solid content concentration and R of the A2 liquid are shown in Table 2.
[0338] The obtained A2 liquid was spray-dried at the same dryer inlet temperature as in Example 2-1 to obtain dry particles.
[0339] Next, the obtained dried particles were molded, dried and calcined in the same manner as in Example 2-1 to obtain a catalyst molded body. The element composition of the catalyst molded body other than oxygen was Mo: 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 , the molar ratio of ammonium radical is 1 or less. In addition, there are two peaks in the range of pore diameter 0.05 to 10 μm in the pore distribution curve. The specific surface area, pore volume and IB / IA in the pore distribution curve of the catalyst molded body are shown in Table 2.
[0340] Next, the obtained molded catalyst was filled in a reaction tube to form a molded catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 2-1. The results are shown in Table 2.
[0341] <Example 2-3>
[0342] Liquid A2 was obtained by the same method as in Example 2-1.
[0343] The obtained A2 liquid was spray-dried at the same dryer inlet temperature as in Example 2-1, and sieved using a sieve with a mesh size of 15 μm, and the dried matter falling under the sieve was used as dried matter particles.
[0344] Next, the obtained dried particles were molded, dried and calcined in the same manner as in Example 2-1 to obtain a catalyst molded body. The element composition of the catalyst molded body other than oxygen was Mo: 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 , the molar ratio of ammonium radical is 1 or less. In addition, there are two peaks in the range of pore diameter 0.05 to 10 μm in the pore distribution curve. The specific surface area, pore volume and IB / IA in the pore distribution curve of the catalyst molded body are shown in Table 2.
[0345] Next, the obtained molded catalyst was filled in a reaction tube to form a molded catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 2-1. The results are shown in Table 2.
[0346] <Example 2-4>
[0347] Liquid A1 was obtained by the same method as in Example 2-1 except that 13.5 parts of cesium carbonate was used instead of 15.7 parts of cesium hydrogen carbonate.
[0348] Next, using this A1 solution, A2 solution was obtained by the same method as in Example 2-1. Table 2 shows the pH, solid content concentration, and R of this A2 solution.
[0349] The obtained A2 liquid was spray-dried at a dryer inlet temperature of 250° C. to obtain dry particles.
[0350] Next, the obtained dried particles were molded, dried and calcined in the same manner as in Example 2-1 to obtain a catalyst molded body. The element composition of the catalyst molded body other than oxygen was Mo: 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4, the molar ratio of ammonium radical is 1 or less. In addition, there are two peaks in the range of pore diameter 0.05 to 10 μm in the pore distribution curve. The specific surface area, pore volume and IB / IA in the pore distribution curve of the catalyst molded body are shown in Table 2.
[0351] Next, the obtained molded catalyst body was filled in a reaction tube to form a molded catalyst body layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 2-1.
[0352] <Example 2-5>
[0353] Liquid A1 was obtained by the same method as in Example 2-1.
[0354] Next, a solution prepared by dissolving 15.0 parts of ammonium carbonate in 20 parts of pure water was added over 21.2 minutes to obtain liquid A2. The v / M at this time, the pH, the solid content concentration and R of the liquid A2 are shown in Table 2.
[0355] The obtained A2 liquid was dried by the same method as in Example 2-1 to obtain dry particles.
[0356] Next, the obtained dried particles were molded, dried and calcined in the same manner as in Example 2-1 to obtain a catalyst molded body. The element composition of the catalyst molded body other than oxygen was Mo: 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 , the molar ratio of ammonium radical is 1 or less. In addition, there are two peaks in the range of pore diameter 0.05 to 10 μm in the pore distribution curve. The specific surface area, pore volume and IB / IA in the pore distribution curve of the catalyst molded body are shown in Table 2.
[0357] Next, the obtained molded catalyst was filled in a reaction tube to form a molded catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 2-1. The results are shown in Table 2.
[0358] <Comparative Example 2-1>
[0359] 400 parts of pure water at 25°C was used as a solvent, and 100 parts of molybdenum trioxide, 7.5 parts of ammonium metavanadate, and 7.0 parts of copper (II) nitrate trihydrate were added. The obtained slurry was heated to 95°C while stirring, and the liquid temperature was maintained at 95°C and stirred for 3 hours. Next, the liquid temperature was lowered to 50°C, and a solution of 15.7 parts of cesium bicarbonate dissolved in 20 parts of pure water was mixed and stirred for 15 minutes while the liquid temperature was maintained at 50°C. Thus, A1' liquid was obtained.
[0360] Next, the temperature of the A1' liquid was maintained at 50°C, and a solution of 15.8 parts of ammonium nitrate dissolved in 20 parts of pure water was added while stirring at 110 rpm using a rotary blade stirrer. The addition took 6.8 minutes. The temperature and v / M of the A1' liquid at this time are shown in Table 2. After the addition was completed, the liquid temperature was further maintained at 95°C and stirred for 15 minutes. 11.4 parts of an 85% by mass phosphoric acid aqueous solution was mixed with the obtained slurry and stirred for 15 minutes to obtain an A2' liquid. The pH, solid content concentration and R of the A2' liquid are shown in Table 2.
[0361] The obtained A2' liquid was spray-dried at the same dryer inlet temperature as in Example 2-1 to obtain dry particles.
[0362] Next, the obtained dried particles were molded, dried and calcined in the same manner as in Example 2-1 to obtain a catalyst molded body. The element composition of the catalyst molded body other than oxygen was Mo: 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 , the molar ratio of ammonium radical is 1 or less. In addition, there are two peaks in the range of pore diameter 0.05 to 10 μm in the pore distribution curve. The specific surface area, pore volume and IB / IA in the pore distribution curve of the catalyst molded body are shown in Table 2.
[0363] Next, the obtained molded catalyst body was filled in a reaction tube to form a molded catalyst body layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 2-1.
[0364] <Comparative Example 2-2>
[0365] Liquid A1' was obtained by the same method as in Comparative Example 2-1 except that 200 parts of pure water at 25° C. was used as the solvent.
[0366] Next, using this A1′ liquid, A2′ liquid was obtained by the same method as in Comparative Example 2-1. Table 2 shows the pH, solid content concentration, and R of this A2′ liquid.
[0367] The obtained A2' liquid was spray-dried at the same dryer inlet temperature as in Example 2-1 to obtain dry particles.
[0368] Next, the obtained dried particles were molded, dried and calcined in the same manner as in Example 2-1 to obtain a catalyst molded body. The element composition of the catalyst molded body other than oxygen was Mo: 12 P 1.7 V1.1 Cu 0.5 Cs 1.4 , the molar ratio of ammonium radical is 1 or less. In addition, there are two peaks in the range of pore diameter 0.05 to 10 μm in the pore distribution curve. The specific surface area, pore volume and IB / IA in the pore distribution curve of the catalyst molded body are shown in Table 2.
[0369] Next, the obtained molded catalyst body was filled in a reaction tube to form a molded catalyst body layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 2-1.
[0370] <Comparative Example 2-3>
[0371] Liquid A1 was obtained by the same method as in Example 2-1.
[0372] Next, the temperature of the A1 liquid was maintained at 95°C, and a solution of 15.0 parts of ammonium carbonate dissolved in 20 parts of pure water was added while stirring at 110 rpm using a rotary blade stirrer. The addition required 105.7 minutes. The temperature and v / M of the A1 liquid at this time are shown in Table 2. After the addition was completed, the liquid temperature was further maintained at 95°C, stirred for 15 minutes, and then heated to 100°C. Next, the liquid temperature was maintained at 100°C and stirred for 40 minutes to obtain the A2 liquid. The pH, solid content concentration and R of the A2 liquid are shown in Table 2.
[0373] The obtained A2 liquid was dried at 140° C. using a drum dryer to obtain dried particles.
[0374] Next, the obtained dried particles were molded, dried and calcined in the same manner as in Example 2-1 to obtain a catalyst molded body. The element composition of the catalyst molded body other than oxygen was Mo: 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 , the molar ratio of ammonium radical is 1 or less. In addition, there are two peaks in the range of pore diameter 0.05 to 10 μm in the pore distribution curve. The specific surface area, pore volume and IB / IA in the pore distribution curve of the catalyst molded body are shown in Table 2.
[0375] Next, the obtained molded catalyst was filled in a reaction tube to form a molded catalyst layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 2-1. The results are shown in Table 2.
[0376] <Comparative Example 2-4>
[0377] Liquid A1 was obtained by the same method as in Example 2-1 except that a solution prepared by dissolving 15.7 parts of cesium hydrogen carbonate in 20 parts of pure water was mixed while stirring at a liquid temperature of 50°C.
[0378] Next, liquid A2' was obtained in the same manner as in Example 2-1 except that a solution of 15.0 parts of ammonium carbonate dissolved in 20 parts of pure water was added over 184.0 minutes. Table 2 shows the v / M at this time, the pH, the solid content concentration and R of the liquid A2'.
[0379] The obtained A2' liquid was dried by the same method as in Example 2-1 to obtain dry particles.
[0380] Next, the obtained dried particles were molded, dried and calcined in the same manner as in Example 2-1 to obtain a catalyst molded body. The element composition of the catalyst molded body other than oxygen was Mo: 12 P 1.7 V 1.1 Cu 0.5 Cs 1.4 , the molar ratio of ammonium radical is 1 or less. In addition, there are two peaks in the range of pore diameter 0.05 to 10 μm in the pore distribution curve. The specific surface area, pore volume and IB / IA in the pore distribution curve of the catalyst molded body are shown in Table 2.
[0381] Next, the obtained molded catalyst body was filled in a reaction tube to form a molded catalyst body layer, and an oxidation reaction of methacrolein was carried out in the same manner as in Example 2-1.
[0382]
[0383] As shown in Table 2, Examples 2-1 to 2-5 in which the pore volume of the catalyst molded body and IB / IA in the pore distribution curve were within the prescribed ranges showed higher methacrylic acid yields than the comparative examples.
[0384] In addition, methacrylic acid ester can be obtained by esterifying the methacrylic acid obtained in Examples 2-1 to 2-5.
[0385] Industrial Applicability
[0386] According to the present invention, a catalyst precursor and a catalyst molded body capable of producing a catalyst capable of producing an α,β-unsaturated carboxylic acid in high yield can be provided.
Claims
1. A catalyst precursor, which is a catalyst precursor comprising a Keggin-type heteropoly acid used when oxidizing an α,β-unsaturated aldehyde to produce an α,β-unsaturated carboxylic acid. Its pore volume is 0.005 to 0.15 mL / g.
2. The catalyst precursor according to claim 1, wherein The median particle size is 1 to 50 μm.
3. The catalyst precursor according to claim 2, wherein The median particle size is 5 to 40 μm.
4. The catalyst precursor according to claim 1, wherein The pore volume is 0.01 to 0.10 mL / g.
5. The catalyst precursor according to claim 1, wherein The bulk density is 1.15~1.6kg / L.
6. The catalyst precursor according to claim 1, which has a composition represented by the following formula (I): Q a Mo b V c Cu d A e HAVE BEEN f G g (NH4) h O i (I) In formula (I), P, Mo, V, Cu, NH4 and O represent phosphorus, molybdenum, vanadium, copper, ammonium and oxygen, respectively; A represents at least one element selected from antimony, bismuth, arsenic, germanium, tellurium, selenium, silicon and tungsten, E represents at least one element selected from iron, zinc, chromium, tantalum, cobalt, nickel, manganese, titanium, niobium and cerium, G represents at least one element selected from lithium, sodium, potassium, rubidium and cesium, a~i represents the molar ratio of each component, satisfying b=12, a=0.5~3, c=0.01~3, d=0.01~2, e=0~3, f=0~3, g=0.01~3, h=1~30, and i is the molar ratio of oxygen required to satisfy the valence of each component.
7. A molded catalyst body, which is used when producing an α,β-unsaturated carboxylic acid by oxidizing an α,β-unsaturated aldehyde, and contains a catalyst component containing phosphorus, molybdenum and vanadium. Its pore volume is 0.01~0.40mL / g, In the pore distribution curve of the catalyst molded body, when the height of the highest peak A having a vertex in the pore diameter range of 0.05 to 10 μm is IA and the height of the second highest peak B is IB, IB / IA is 0.160 to 0.
420.
8. The catalyst molded body according to claim 7, wherein The IB / IA is 0.200 to 0.
400.
9. The catalyst molded body according to claim 7, wherein Specific surface area is 1~10m 2 / g.
10. The catalyst molded body according to claim 9, wherein The specific surface area is 1.5 to 8 m 2 / g.
11. The catalyst molded body according to claim 7, wherein The pore volume is 0.10 to 0.35 mL / g.
12. The catalyst molded body according to claim 7, wherein The apexes of the peak A and the peak B exist in the range of pore diameters of 0.08 to 8 μm. The catalyst molded body according to claim 7 , which is an extruded molded body.
14. A method for producing a catalyst precursor, which is the method for producing a catalyst precursor according to claim 1, comprising: Step (i), obtaining a solution or slurry containing phosphorus, molybdenum and vanadium, i.e., liquid A1, Step (ii), adding a raw material compound containing ammonium radicals, i.e. compound B, to the A1 solution to obtain a slurry, i.e., A2 solution, having a pH of 3 or less, and Step (iii), drying the A2 solution to obtain dry particles, In the step (ii), compound B is added in a manner satisfying the following formula (II): v / M=0.10~1.80(II) In formula (II), M is the number of moles of molybdenum contained in the A1 solution and its unit is mol, and v is the addition rate of ammonium ions and its unit is mol / h.
15. A method for producing a catalyst molded body, wherein the catalyst molded body is obtained from the catalyst precursor produced by the method according to claim 14, comprising: In step (iv), the dried particles are extruded to obtain a catalyst molded body.
16. A method for producing a catalyst, comprising calcining the catalyst precursor according to any one of claims 1 to 6 or the catalyst precursor produced by the method according to claim 14.
17. A method for producing a catalyst molded body, which is the method for producing a catalyst molded body according to claim 7, comprising: Step (i), obtaining a solution or slurry containing phosphorus, molybdenum and vanadium, i.e., liquid A1, Step (ii), adding a raw material compound containing ammonium radicals, i.e. compound B, to the A1 solution to obtain a slurry, i.e., A2 solution, having a pH of 3 or less, Step (iii), drying the A2 solution to obtain dry particles, and Step (iv), extruding and molding the dried particles to obtain a catalyst molded body, In the step (ii), compound B is added in a manner satisfying the following formula (II): v / M=0.10~1.80(II) In formula (II), M is the number of moles of molybdenum contained in the A1 solution and the unit is mol, and v is the addition rate of ammonium ions and the unit is mol / h.
18. The method for producing a molded catalyst according to claim 15 or 17, wherein: The solid content concentration of the A2 liquid is 30% by mass or less.
19. The method for producing a molded catalyst according to claim 15 or 17, wherein: When the ratio of the total mass of the dissolved molybdenum element, phosphorus element, and vanadium element to the total mass of the molybdenum element, phosphorus element, and vanadium element in the A2 liquid is represented by R, R is 5 to 25 mass %.
20. The method for producing a catalyst molded body according to claim 15 or 17, wherein: In the step (ii), compound B is added to the A1 solution at a temperature of 90 to 99° C. while stirring at a rotation speed of 70 to 140 rpm.
21. The method for producing a catalyst molded body according to claim 15 or 17, wherein: In the step (iii), the A2 solution is spray-dried.
22. The method for producing a catalyst molded body according to claim 15 or 17, wherein: The step (iv) comprises the following steps (iv-1) and (iv-2): Step (iv-1), mixing the dry particles, liquid and a binder to obtain a kneaded product, In step (iv-2), the kneaded product is extruded and molded using an extruder to obtain a catalyst molded body.
23. The method for producing a catalyst molded body according to claim 22, wherein: In the step (iv-1), 15 to 60 parts by mass of the liquid and 0.05 to 15 parts by mass of the binder are mixed with 100 parts by mass of the dry particles.
24. The method for producing a catalyst molded body according to claim 22, wherein: In the above (iv-2), extrusion molding is performed at an extrusion pressure of 0.1 to 30 MPa.
25. A method for producing an α,β-unsaturated carboxylic acid, comprising oxidizing an α,β-unsaturated aldehyde using a catalyst obtained by molding and / or calcining the catalyst precursor according to any one of claims 1 to 6 or a catalyst molded body according to any one of claims 7 to 13 to produce an α,β-unsaturated carboxylic acid. 26 . A method for producing an α,β-unsaturated carboxylic acid ester, comprising esterifying the α,β-unsaturated carboxylic acid produced by the method according to claim 25 .
Citation Information
Patent Citations
Catalyst of synthesis of methacrylic acid and preparation thereof showing excellent reproducibility
JP1988315148A
Catalyst for producing methacrylic acid, production thereof and production of methacrylic acid
JP2000084412A
Method for manufacturing methacrylic acid producing catalyst
JP2011224482A
Method for preparing catalyst for production of methacrylic acid
WO2012141076A1